Multiphysics modelling of MICP grouting for drawdown control and curtain stability in confined aquifers with partially penetrating barriers during deep excavation - Sharif Nyanzi Alidekyi; Jianxiu Wang; Weiqiang Pan; Muhammad Arslan Ahmad; Yanxia Long; Naveed Sarwar Abbasi; Aamir Khan Mastoi (Computers and Geotechnics, 2027)

Expression of wild-type and recombinant D4-CK domains of VWF gene with novel variants in Pakistan - Arshia Latif; Muhammad Asif Naveed; N. A. Shabana (Molecular Biology Reports, 2026)

High frequency and prognostic significance of TP53 promoter methylation in Pakistani glioblastoma patients - Ahad Naveed; Noor Muhammad; Afshan Khanum; Asif Loya; Muhammad Usman Rashid (Molecular Biology Reports, 2026)

Immunoinformatics-guided design of a multi-epitope vaccine targeting the envelopment polyprotein of oropouche virus - Muhammad Naveed; Aroosa Athar; Afifa Tariq; Muhammad Asim; Muhammad Nouman Majeed; Rania Ali El Hadi Mohamed; Manal F. Elkhadragy; Maher S. Alwethaynani; Mai M. Almsaud; Ghulam Nabi (Molecular Genetics and Genomics, 2026)

Phytochemical Analysis, Antioxidant and Pharmacological Evaluation of Antidiabetic Activity of Methanolic Extract of Geranium wallichianum D. Don ex Sweet in Alloxan-Induced Diabetic Rats - Fatima Afzal; Abdul Aleem; Javed Iqbal; Fahad Asim; Irfan Anjum; Muhammad Naveed Mushtaq (Journal of Pharmaceutical Innovation, 2026)

Genome-wide characterization and comparative analysis of Bacillus paranthracis MBBL1 reveals genomic plasticity features - Nimra Hanif; Muhammad Naveed; Maida Salah Ud Din; Tariq Aziz; Ashwag Shami; Fakhria A. Al-Joufi (Functional & Integrative Genomics, 2026)

Moderate maize canopy defoliation improves light distribution, crop yields, and soybean seed quality in additive maize-soybean intercropping - Muhammad Ali Raza; Wang Zhiqi; Amjad Saeed; Hina Gul; Hassan Shehryar Yasin; Asif Naveed Ranjha; Zaheer Ahmed; Ghulam Raza; Wopke Van Der Werf; Akash Fatima; Xue Liang; Muhammad Hayder Bin Khalid; et al. (Field Crops Research, 2026)

Strait of Hormuz disruption, geopolitical dispute intensity and Brent-based hedging effectiveness in European fuel markets: Empirical evidence from DCC-GARCH approach - Hafiz Muhammad Naveed; Huaping Sun; Muhammad Shahid; Rabia Akram; Zaiba Ali (Energy Policy, 2026)

Numerical analysis of Soret and Dufour effects in chemically reactive bioconvective flow through a converging–diverging channel - Muhammad Naveed Khan; Karim Choubani; Shafiq Ahmad; Hongchu Chen; Mohammed A. Almeshaal (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Defect engineering of complex perovskite oxide via plasmonic metal (La0.6Sr0.4Fe0.7Cu0.1Co0.2O3) in polymeric network hydrogel for enhanced solar steam generation - Naila Arshad; Muhammad Sultan Irshad; Lamia Abu El Maati; Afraa Alotaibi; Van-Duong Dao; Naveed Mushtaq; Muneerah Alomar (Journal of Environmental Chemical Engineering, 2026)

Groundwater Contamination and Probabilistic Health Risk Assessment of Heavy Metals in Coal Mining Areas of Punjab, Pakistan - Aima Iram Batool; Muhammad FayyazUrRehman; Naima Huma Naveed; Javaria Ikram; Hakim Bibi (Water, Air, & Soil Pollution, 2026)

Bacillus subtilis MGRP21 mitigates chromium induced oxidative stress and enhances biomass of Brassica napus L - Shurmeen Qammar; Syeda Sadaf Zehra; Muhammad Naveed Aslam; Anam Moosa; Phyu Shin Thant; Tahir Mahmood; Hongwei Zhao (Physiological and Molecular Plant Pathology, 2026)

Agrobacterium tumefaciens-mediated stable transformation of CP4 EPSPS gene conferring glyphosate resistance in Zea mays L - Muhammad Atif; Hammad Ahmed Abbasi; Muhammad Naveed Anjum (Ecological Genetics and Genomics, 2026)

In silico pharmacological evaluation of a multi-epitope vaccine candidate targeting the G1 and G2 glycoproteins of Oropouche virus via TLR3 interaction - Khadija Khawar; Komal Imran; Muhammad Aamir Sharif; Muhammad Naveed; Nantenaina Tombozara; Maha A. Alwaili; ‏Mariam A. Alkhateeb; Seham O. Alsulami (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Retraction Note: Matrine alleviates neurobehavioral alterations via modulation of JNK-mediated caspase-3 and BDNF/VEGF signaling in a mouse model of burn injury - Adnan Khan; Bushra Shal; Muhammad Naveed; Bakht Nasir; Nadeem Irshad; Hussain Ali; Salman Khan (Psychopharmacology, 2026)

Formulation and Evaluation of Losartan Potassium Microparticles Loaded Controlled-Release Tablets: An In-Vitro Perspective - Kamran Ahmad Khan; Ashfaq Ahmad; Muhammad Israr; Saima Mahmood; Farman Shah; Naveed Ullah; Fida Muhammad; Anam Adil; Sami ul Haq; Haroon Khan (Journal of Pharmaceutical Innovation, 2026)

Revolutionizing the potential of laccase from Bacillus paralicheniformis as an eco-friendly solution to reduce polychlorinated dibenzofurans contamination through integrated computational approach - Muhammad Naveed; Ayesha Saleem; Tariq Aziz; Urooj Rasheed; Arooj Azeem; Maryum Rasheed; Manal F. Elkhadragy; Ashwag Shami; Hanan Abdulrahman Sagini; Rewaa S. Jalal; Hayam A. Alwabsi; Fakhria A. Al-Joufi (Biodegradation, 2026)

Multifunctional Bacterial Cultures Dissipate Glyphosate and Improve Nutrient Uptake, Growth, Physiology, and Yield Dynamics of Mungbean in the Contaminated Soil - Qammar Farooq; Muhammad Imran Khan; Muhammad Naveed; Irfan Ahmad (Journal of Soil Science and Plant Nutrition, 2026)

Retraction Note: Bi-polymeric Spongy Matrices Through Cross-linking Polymerization: Synthesized and Evaluated for Solubility Enhancement of Acyclovir - Saima Asghar; Naveed Akhtar; Muhammad Usman Minhas; Kifayat Ullah Khan (AAPS PharmSciTech, 2026)

Comparative in vitro pathogenicity of different oil-based formulations of Metarhizium anisopliae against three different aphid species - Ahmad Nawaz; Anam Ejaz; Tariq Mustafa; Usman Naeem; Amna Irshad; Muhammad Dildar Gogi; Muhammad Tayyib; Muhammad Naveed; Amjad Abbas; Muhammad Jalal Arif (International Journal of Tropical Insect Science, 2026)

Lessons learned from the modeling of nature-based solutions for urban flood mitigation in Ottawa, Canada - Ali Zoghi; Ryan Cooke; Muhammad Naveed Khaliq; Jennifer Drake (Journal of Hydrology, 2026)

Corrigendum to “Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes” [Fuel 412 (2025) 138022] - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Tailoring SrFeO3-δ cathodes via Nd and Cu doping for boosting ORR activity for high-performance LT-PCFCs below 600 °C - Naveed Mushtaq; Wu Ping; Badriah S. Almutairi; Sajid Rauf; M.A.K Yousaf Shah; Muhammad Sultan Irshad (Fuel, 2026)

Genomic characterization of an isolate of tomato leaf curl New Delhi virus associated with tomato crops - Abdul Majid; Muhammad Taimoor Shakeel; Muhammad Naveed Aslam; Ambreen Maqsood; Muhammad Raheel; Waqas Ashraf; Tahir Farooq; Atta ur Rehman Khan; Mahmoud Ahmed Amer; Mohammed Ali Al-Saleh (European Journal of Plant Pathology, 2026)

Correction: Molecular characterization and green synthesis of iron oxide nanoparticles from Ureibacillus chungkukjangi for methylene blue degradation - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Shumaila Ibrahim; Maida Salah Ud Din; Maryam M. Alomran; Ashwag Shami; Fakhria A. Al-Joufi; Ahmad A. Alghamdi; Abdullah A. Alqasem; Ahmed M. Basri; Majid Alhomrani (Antonie van Leeuwenhoek, 2026)

Spatio-temporal analysis of land surface temperature, urban heat island intensity, and urban thermal field variance index in Faisalabad, Pakistan - Muhammad Naveed; Bilal Hussain; Awais Ali; Ayesha Mariam; Abdul Ghafoor; Fozia Allah Ditta; Basharat Ali (Air Quality, Atmosphere & Health, 2026)

Trends and Disparities in Mortality from Hereditary Ataxia in United States, 2000–2020: A Retrospective Analysis with Projections to 2050 - Muhammad Junaid Iqbal; Fiza Wali; Laraib Israr; Noor Ullah Khan; Hanzala Ahmed Farooqi; Fatima Naveed; Areeba Kabir; Gianluca Morganti; Anastasia Ricci; Michele Menotta (The Cerebellum, 2026)

Structure-based immunopharmacological design of a multi-epitope vaccine candidate against Naegleria fowleri targeting TLR3: a pan-genomic and molecular dynamics approach - Rabia Faizan; Muhammad Naveed; Inmaculada Bellido Estevez; Hafiz Muzzammel Rehman; Ayesha Latif; Hafiz Muhammad Hammad; Abdul Rafay Khan; Seham O. Alsulami; Maha A. Aljumaa; Nantenaina Tombozara (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Developmental Toxicity of Lead and Copper in Chick Embryos: Morphometric and Histological Assessment of In Ovo Exposure - Aima Iram Batool; Noor Fatima; Muhammad Fayyaz Ur Rehman; Naima Huma Naveed; Javaria Ikram; Iram Inayat (Biological Trace Element Research, 2026)

Influence of weather patterns on ground-level ozone pollution: a 2023 summer case study in Jilin City with health risk assessment - Anees Akhtar; Chunsheng Fang; Ju Wang; Sarfraz Ahmed; Muhammad Awais Haider; Haider Ali; Muhammad Naveed; Samama Tariq (Environmental Monitoring and Assessment, 2026)

Immunopharmacological and structural design of a polyprotein based multi epitope vaccine against Powassan virus - Aasia Kalsoom; Syed Hussain Abidi; Sohail Ameer Marwat; Ghulam Shabbir; Muhammad Naveed; Aiman Muhammad Ashraf Mughal; Muhammad Nouman Majeed; Shereen Magdy Korany; Basma Magdy Korany; Khaled Alzhrani; Tariq Aziz (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Design and development of a low-cost industrial prototype of spot-specific spraying system for potato weed detection using deep learning - Faiza Khan; Muhammad Naveed Tahir; Muhammad Aqib; Yubin Lan; Noureen Zafar; Shoaib Saleem; Zainab Haroon; Wenjiang Huang (Computers and Electronics in Agriculture, 2026)

Corrigendum to “Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes”. [Fuel 412 (2025) 138022. doi: 10.1016/j.fuel.2025.138022] - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Retraction notice to “Dual Z-scheme core-shell PANI-CeO2-Fe2O3-NiO heterostructured nanocomposite for dyes remediation under sunlight and bacterial disinfection” [Environ. Res. 215 (2022) 114140] - Faisal Mukhtar; Tauseef Munawar; Muhammad Shahid Nadeem; Muhammad Naveed ur Rehman; Shoukat Alim Khan; Muammer Koc; Sana Batool; Murtaza Hasan; Faisal Iqbal (Environmental Research, 2026)

Microplastics as Trojan horses: Vectors of pathogens, pollutants, and antimicrobial resistance genes - Ghazala Saeed; Ali Afzal; Afzal Nimra; Zaira Ahmad; Amna Rehman; Kaleem Maqsood; Tayyba Jan; Muhammad Ishfaq Ahmad; Naveed Karim; Byong-Hun Jeon; Ghulam Mustafa; Fakhar Zaman; et al. (Environmental Research, 2026)

Thermal analysis of nonsymmetric stress tensor on a partially ionized viscoelastic non-Newtonian fluid flow with convective boundary conditions (A numerical study) - Muhammad Naveed Khan; Aamir Abbas Khan; Haifaa F. Alrihieli; Walid Abdelfattah; Ibrahim E. Elseesy (Dynamics of Atmospheres and Oceans, 2026)

Correction: Soil C/P Stoichiometry Mediated Microbially Driven Phosphorus Mobilization: New Insight in Soil P Management - Khuram Shehzad Khan; Muhammad Naveed; Allah Ditta; Tajwar Alam; Muhammad Zahid Mumtaz; Aown Abbas; Lingling Li (Journal of Soil Science and Plant Nutrition, 2026)

Fabrication and In-Vitro and In-Vivo Assessment of Levofloxacin Beads Loaded Floating Tablets to improve Gastric Residence Time - Muhammad Israr; Kamran Ahmad Khan; Ashfaq Ahmad; Kifayat Ullah Shah; Naveed Ullah; Naheed Akhtar (Journal of Pharmaceutical Innovation, 2026)

Fabrication, Preparation and In-Vitro and In-Vivo Evaluation of Metoprolol Tartrate Controlled-Release Matrices to Establish a Correlation - Kamran Ahmad Khan; Ashfaq Ahmad; Muhammad Israr; Saima Mahmood; Sami-ul-Huq; Naveed Ullah; Anam Adil; Fida Muhammad (Journal of Pharmaceutical Innovation, 2026)

Physical and high-temperature rheological properties of asphalt binder incorporating waste engine oil modifier - Raza Mehmood; Fauzan Mohd Jakarni; Ratnasamy Muniandy; Salihudin Hassim; Nik Norsyahariati Nik Daud; Anwaar Hazoor Ansari; Zafreen Elahi; Muhammad Naveed (Innovative Infrastructure Solutions, 2026)

Geospatial analysis of surface urban heat island dynamics and land use changes in Pakistan using multi-spectral indices - Awais Ali; Bilal Hussain; Muhammad Naveed; Bader Alshehri; Abdul Ghafoor; Zeeshan Zafar; Faisal Sultan Qadri (Advances in Space Research, 2026)

Decoding the catalytic potential of a Cycloclasticus zancles ring-hydroxylating dioxygenase through computational analysis for enhanced PAH biodegradation - Muhammad Naveed; Ahmed Raza; Ahiba Adil; Abubakar Majeed; Sana Miraj Khan; Ayaz Ali Khan; Rania Ali El Hadi Mohamed; Nawal H. Siddig; Hayam A. Alwabsi; Hanan Abdulrahman Sagini (Biodegradation, 2026)

In silico evaluation of protocatechuate 4,5-dioxygenase for environmental detoxification of persistent organic pollutants - Muhammad Naveed; Maryum Rasheed; Maida Salah Ud Din; Minahil Zahid; Ayaz Ali Khan; Mayasar I. Al Zaban; Ashwag Shami; Hayam A. Alwabsi (Biodegradation, 2026)

Cortinarius squamibrunneus sp. nov. ( Basidiomycota ; Agaricales ) in C . Section Safranopedes of Subgenus Telamonia from Swat District, Khyber Pakhtunkhwa, Pakistan - Hira Ijaz; Tasneem Ashraf; Muhammad Naveed; Gul Sanga; Sadiq Ullah; Sana Jabeen (New Zealand Journal of Botany, 2026)
Cortinarius squamibrunneus sp. nov. was collected from Swat District, Khyber Pakhtunkhwa, Pakistan. The species is distinguished from its closely related species, C . epipurrus , by its pale orangish‐brown to brown, fibrillose–squamulose pileus with a darker central disc and a rimose to radially cracked margin, smaller basidiospores (5.5–7.4 × 3.6–5 μm) with finely ornamented warts and variably shaped sterile cells. Comparative morphological analyses combined with molecular phylogenetic inference based on the ITS region of nrDNA confirm that this taxon is distinct from previously described species and represents a new species within C. sect. Safranopedes of C . subg. Telamonia .

Integrative 16S rRNA characterization, pan-genome, and immunoinformatics approaches for the design of a multi-epitope vaccine against Bacillus cereus, a foodborne pathogen - Muhammad Asim; Muhammad Naveed; Tariq Aziz; Muhammad Toheed; Hafiz Muzzammel Rehman; Nawal Al-Hoshani; Rania Ali El Hadi Mohamed; Maher S. Alwethaynani; Areej A Alhhazmi; Manal F. Elkhadragy (World Journal of Microbiology and Biotechnology, 2026)

Precision Agriculture Through Green Nanoparticles: Mechanistic Insights into Nutrient Delivery and Enzyme-Targeted Pest Control with Emerging Computational Perspectives - Muhammad Irfan; Hira Altaf; Mishal Naveed; Nadia Zeeshan; Umer Rashid; Amber Afroz (Journal of Soil Science and Plant Nutrition, 2026)

Titanium dioxide nanoparticles as a sustainable strategy to control root-knot nematodes (RKNs) in tomato (Solanum lycopersicum L.) - Asma Mehak; Abida Akram; Amjad Ali; Naveed Iqbal Raja; Tariq Mukhtar; Jaya Seelan Sathiya Seelan; Muhammad Shahbaz (Physiological and Molecular Plant Pathology, 2026)

Biogenic silver-selenium nanocomposites as an effective and sustainable alternative for controlling citrus canker - Iqra Ilyas; Hammad Ul Hassan; Naveed Iqbal Raja; Zia-Ur-Rehman Mashwani; Hossam S. El-Beltagi; Muhammad Sheeraz Ahmad; Huma Qureshi; Tauseef Anwar; Muhammad Iqbal; Khalid H. Alamer; Nazih Y. Rebouh; Bakhrom Jobborov; et al. (Physiological and Molecular Plant Pathology, 2026)

Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Elucidating the metabolic network and pH-dependent biosynthesis of bioactive exopolysaccharides XY1-EPS in Bacillus smithii - Nan Zhao; Xinyue Fan; Muhammad Naveed Sheas; Ting Yu; Fujie Yan (Carbohydrate Polymers, 2026)

Protective potential of linalool against cyclophosphamide-induced interstitial cystitis: mechanistic insights from experimental and computational approaches - Irfan Anjum; Asfia Arooje; Saima; Fawad Naeem; Muhammad Naveed Mushtaq; Kashif Barkat; Zaka Ur Rehman; Syed Damin Abbas Hamdani; Shah Jahan; Mohammed Dauelbait; Amir Bouallegue; Esmael M. Alyami; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Multidrug-resistant Staphylococcus aureus robustly activates the complement system but resists downstream effector mechanisms - Muhammad Naveed; Sadia Akbar; Isfahan Tauseef; Abdul Majid; Fazal Ullah; Kashif Syed Haleem (Archives of Microbiology, 2026)

Greening the future: deep intelligent neural networks-based analysis of green finance in renewable energy and environmental degradation in emerging economies - Hafiz Muhammad Naveed; Yanchun Pan; Arshian Sharif; Muhammad Farhan Bashir; Mamdouh Abdulaziz Saleh Al-Faryan (Environment, Development and Sustainability, 2026)

Impacts of climate change and local stressors on the coral community structure off the eastern coast of Pakistan - Amjad Ali; Azka Rafiq Malik; Naveed Ahmad; Gulab Said; Zulfiqar Ali Mirani; Seema Shafique; Habibul Hassan; Ateeque Rahman Khooharo; Faiz Muhammad (Regional Studies in Marine Science, 2026)

Spatiotemporal lag effects between vegetation dynamics and climate variability on the Tibetan Plateau during 2001–2024 - Zulqarnain Satti; Yipeng Wang; Peng Shen; Muhammad Naveed; Muhammad Burhan Memon; Muhammad Shafeeque; Chong Fan; Heifeng Li (Remote Sensing Applications: Society and Environment, 2026)

Broad-Spectrum Antibacterial Action of Lipopeptides Derived from Bacillus smithii by Targeting Quorum Sensing - Nan Zhao; Xinyue Fan; Muhammad Naveed Sheas; Ting Yu; Fujie Yan (Probiotics and Antimicrobial Proteins, 2026)

Decoding core molecular mechanisms of heat-stress tolerance in Brassica napus using transcriptomics and machine learning - Muhammad Ikram; Muhammad Farhan; Behnam Derakhshani; Sunjeet Kumar; Aliya Ayaz; Naveed Khan; Enerand Mackon; Babar Usman; Si Chengcheng; Pingwu Liu (Plant Cell Reports, 2026)

Formulation Design of Glucuronoxylan-Based Stimuli-Responsive Microparticles for Zero-Order Drug Delivery - Saleha Babar; Fatima Akbar Sheikh; Syed Nasir Abbas Bukhari; Muhammad Tahir Haseeb; Arshad Ali; Nisar Ul Khaliq; Ranya Abdulrahman Alafar; Mohamed Abdelwahab Abdelgawad; Ameeduzzafar Zafar; Naveed Ahmad (Journal of Pharmaceutical Innovation, 2026)

Integrative Molecular and Structural Profiling of Escherichia coli Virulence Genes in Diabetes-Associated Infections - Noor Jahan Begum; Muhammad Qasim; Ihtisham Ul Haq; Hassan Naveed; Farhan Anwar Khan; Zahid Ullah Khan; Farman Ullah Dawar (Current Microbiology, 2026)

Exploring the biocatalytic potential of Amycolatopsis japonica DyP in degrading plasticizer and phenolic-derived xenobiotic compounds - Muhammad Naveed; Ayesha Saleem; Tariq Aziz; Sadia Jabeen; Sana Miraj Khan; Maida Salah Ud Din; Nantenaina Tombozara; Mayasar I. Al-zaban; Ashwag Shami; Hayam A. Alwabsi (Biodegradation, 2026)

Optimization of Tissue Culture Media for Microtuber Development Incorporating Sugars and Zinc Nanoparticles - Muzammil Anwar Khan; Naima Huma Naveed; Aamir Ali; Muhammad Adeel; Aima Iram Batool; Tahir Shahzad; Muhammad Rizwan Khan; Salman Majeed (American Journal of Potato Research, 2026)

Retraction Note: Demystifying the association between economic development, transportation, tourism, renewable energy, and ecological footprint in Bay of Bengal Initiative for Multi-Sectoral Technical and Economic Cooperation region during globalization mode - Muhammad Naveed; Minhazul Islam; Muhammad Usman; Mustafa Kamal; Mohammad Faisal Khan (Environmental Science and Pollution Research, 2026)

Root traits and rhizosphere responses as emerging bioindicators of microplastic pollution in agricultural soils: A review - Qudsia Saeed; Xiankai Lu; Zia Ur Rahman Farooqi; Abdul Ghafoor; Muhammad Naveed; Nimra Maqsood; Hafiz Abdul Kareem; Adnan Mustafa (Environmental Research, 2026)

Characterizing global air pollution seasonality and trends through integrated satellite and meteorological analytics - Muhammad Naveed; Zulqarnain Satti; Muhammad Mateen Tahir; Qazi Muhammad Yasir; Hui Li; Faming Wang (Environmental Pollution, 2026)

Investigation of heat and mass transfer in an electromagnetically driven ionized tri-hybrid nanofluids flow over a convectively heated cylinder - Muhammad Naveed Khan; Shafiq Ahmad; Aamir Abbas Khan; Mounirah Areshi; Ibrahim E. Elseesy (Dynamics of Atmospheres and Oceans, 2026)

Biosynthesis and Biological Assessment of TiO₂ Nanoparticles from Pittosporum Tobira for Antioxidant, Anti-Inflammatory, Anti-Hemolytic Potential, and Polychlorinated Biphenyls Degradation - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Saman Nasir; Maida Salah Ud Din; Nawal Al-Hoshani; Maher S. Alwethaynani; Maymounah A. Alrayyani; Fakhria A. Al-Joufi (Water, Air, & Soil Pollution, 2026)

The gut–liver–virus axis in hepatitis B and C: microbiota, immunometabolism, and exosome-mediated therapeutic opportunities - Kainat Raziq; Syed Qaswar Ali Shah; Mirza Naveed Shahzad; Umm E. Ummara; Mishal Subhan; Muhammad Muzammil Nazir (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A comparative analysis of tsunami flow through emergent and submerged coastal vegetation using numerical simulation - Syed Muhammad Ahmad Bukhari; Naveed Anjum; Saad Abbas; Adnan Shahid; Abdul Basit Bukhari; Ghufran Ahmed Pasha (Natural Hazards, 2026)

Optimizing Phosphorus Use Efficiency and Fodder Yield of Pearl Millet: Two-Year Field Evaluation of Phosphorus-Solubilizing Bacteria with Inorganic Fertilizer Under Alkaline-Calcareous Soils - Abdul Majeed; Qasim Ali; Muhammad Haseeb Javaid; Muhammad Naveed; Mubshar Hussain (International Journal of Plant Production, 2026)

Retraction Note: Novel acetamide derivatives of 2-aminobenzimidazole prevent inflammatory arthritis in rats via suppression of pro-inflammatory mediators - Aymun Madni Zubair; Muhammad Nasir Hayat Malik; Waqas Younis; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Alamgeer Yuchi; Muhammad Naveed Mushtaq; Romeeza Tahir; Muhammad Bilal Sarwar; Muhammad Roman; Ayaz Ali Khan; et al. (Inflammopharmacology, 2026)

Wetland Transformation and Waterfowl Decline: Linking Habitat Change to Northern Pintail Losses in Punjab - Nayyar Batool; Aima Iram Batool; Muhammad Fayyaz Ur Rehman; Misbah Sarwar; Javaria Ikram; Naima Huma Naveed; Iram Inayat; Shaheen Riaz; Hakim Bibi (Environmental Management, 2026)

Eco-Friendly Synthesis of Magnesium Oxide Nanoparticles Using Citrullus colocynthis and their Synergistic Antimicrobial Activity against Drug-Resistant Pathogens - Maqsood Qaisar; Abdul Rehman; Iffat Naz; Hassan Naveed; Baharullah Khattak; Muhammad Qasim (Current Microbiology, 2026)

Molecular Detection and Phylogenetic Characterization of Avian Infectious Bronchitis Virus (IBV) in Vaccinated Commercial Chicken Flocks Experiencing Outbreaks in Faisalabad, Pakistan - Muhammad Mubeen Ahmad; Muhammad Wasif Gulzar; Muhammad Wasif Azeem; Muhammad Musa Mubashar; Rida Fatima; Muhammad Tayyab Naveed; Muhammad Taha; Sana Riaz; Asad Javed; Mudasser Habib; Rizwan Aslam (Archives of Virology, 2026)

Greener hydrogen production and storage revolution towards a low-carbon future: an overview of current scenarios and future prospects - Tahir Rasheed; Sameera Shafi; Muhammad Tuoqeer Anwar; Hifsa Khurshid; Ahmad Naveed; Adil Alshoaibi; Nisrin Alnaim; Yunjian Liu; Tauqir A. Sherazi (Fuel, 2026)

Prediction of Uniaxial Compressive Strength from Petrographic Features of Kirana Dolerites Using a Hybrid Group Method of Data Handling-Levenberg–Marquardt (GMDH-LM) Model - Javid Hussain; Nafees Ali; Xiaodong Fu; Jian Chen; Naveed Ahmad Khan; Sartaj Hussain; Sayed Muhammad Iqbal (Rock Mechanics and Rock Engineering, 2026)

Aflatoxin surveillance in Punjab’s dairy sector: feed and milk contamination - Naveed Akbar; Farhan Saeed; Muhammad Atif Randhawa; Sanaullah Iqbal; Asif Meraj; Abhayveer Singh; Bushra Niaz; T. Krithiga; Rajashree Panigrahi; Amara Rasheed; Zunaira Basharat; Muhammad Afzaal; et al. (Mycotoxin Research, 2026)

Relation of aflatoxin M1 contamination with milk production, health, and reproductive performance of commercial dairy herds in Punjab, Pakistan - Talat Naseer Pasha; Muhammad Uzair Akhtar; Muhammad Naveed ul Haque (Mycotoxin Research, 2026)

Truncated Variants in FAM20A and WDR72 Genes Underlie Autosomal Recessive Amelogenesis Imperfecta in Four Pakistani Families - Sadaqat Ullah; Sher Alam Khan; Samin Jan; Salah Ud Din; Nazif Muhammad; Zia Ur Rehman; Abid Jan; Muhammad Tariq; Noor Muhammad; Abdul Ghani; Naveed Wasif; Saadullah Khan (Biochemical Genetics, 2026)
Amelogenesis Imperfecta (AI) is a set of hereditary diseases affecting enamel development, leading to various types of enamel defects, potentially impacting oral health unassociated with other generalized defects. AI manifests in syndromic and non-syndromic forms and can be inherited through autosomal recessive, autosomal dominant, or X-linked inheritance patterns. Genetic studies have identified sequence variants in a number of genes (≥ 70) linked to both syndromic and non-syndromic AI, highlighting the genetic diversity underlying the condition. The current study involved clinical evaluation and exome sequencing, aimed at identifying the causative variants in four unrelated consanguineous Pakistani families presenting AI phenotypes. The exome sequencing results revealed a novel homozygous frameshift variant FAM20A : NM_017565.4, c.188dupA; p.(Asp63Glufs*17) in families A, B, and C while a nonsense homozygous variant WDR72 : NM_182758.4, c.2686C > T; p. (Arg896*) in family D. The segregation of both variants was confirmed by Sanger sequencing. Bioinformatics analysis predicted the pathogenicity of these genetic variants. These alterations suggest functional consequences, potentially impairing the FAM20A and WDR72 proteins and causing dental anomalies. This investigation significantly broadens our understanding of FAM20A and WDR72 ’s involvement in AI. Furthermore, this study highlights the genetic heterogeneity of AI (involving FAM20A and WDR72 in this study) within the Pakistani population.

Molecular identification of the blaOXA gene in Bacillus cereus and AI-driven optimization of natural phytochemicals for foodborne illness treatment - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Maida Salah Ud Din; Muhammad Nouman Majeed; Ammena Y. Binsaleh; Nawal Al-Hoshani; Maher S. Alwethaynani; Abeer M. Alghamdi; Fakhria A. Al-Joufi (Antonie van Leeuwenhoek, 2026)

Marine Drug Design for Epitheliocytis Rendering AI ‐Assisted Bioisosteric Replacement of Salicin - Muhammad Naveed; Khushbakht Javed; Tariq Aziz; Rahmana Wazir; Imran Ali; Ayaz Ali Khan; Ashwag Shami; Maher S. Alwethaynani; Fahad Al‐Asmari; Fakhria A. Al‐Joufi (Journal of Fish Diseases, 2026)
Epitheliocystis is a distinctive and relatively understudied bacterial infection of finfish skin and gill epithelia that occurs intracellularly and results in the enlargement of the host cells. The Candidatus Syngnamydia salmonis is a bacterial pathogen that affects fish, especially salmon species like trout and salmon. The production of Epitheliocystis by Candidatus Syngnamydia salmonis poses several challenges to the aquaculture industry. Currently, limited drugs and therapies are available to effectively manage and cease the spread of this disease. The goal of this study was to develop a potential drug target for the treatment of epitheliocystis. Salicin, an organic glucoside widely known for its anti‐inflammatory characteristics, was chosen as the initial compound because of its pharmacological significance and confirmed as a bioisostere (a compound with identical biological activities but a different structure). The Xundrug MolOpt AI generative model of bioisosteric replacement tool was chosen as the optimisation technique in a cognitive exertion to improve the novel drug candidate salicin by its AI‐assisted bioisosteric replacement. To retrieve the docking results, the top three ligands from Xundrug and the cell division protein of Candidatus Syngnamydia salmonis were uploaded to the HDOCK web server, which utilises a hybrid docking technique combining template‐based modelling for docking. The target drug candidate was selected based on model 17's highest docking score of 135.6 kcal/mol. Furthermore, the Lipinski rule of five and the ADMET properties of the Bioisosteric Replaced Salicin model 17 (BRS‐17) were carefully explored. The results showed that BRS‐17 fulfilled the pharmacophore characteristics criteria, hence making it an ideal target candidate for Candidatus Syngnamydia salmonis' cell division protein. Additionally, the results are supported by −6.735Kcal/mol docking score predicted by DockThor. With the help of the supporting information from this study, the proposed drug design can close the gap in earlier studies for resistance to antibiotic treatments. It is suggested that in vitro tests be performed on this drug to show the effectiveness of the suggested design.

Assessing the impact of nano-pollutants on the growth and development of stream breeding frogs - Isma Maqbool; Laraib Khadija; Muhammad Rais; Anila Rahim; Luqman; Muhammad Naveed Iqbal Raja; Zia-ur-Rehman Mashwani; Muhammad Shahbaz; Sumbul Gill; Muhammad Saeed (Biologia, 2026)

Machine learning-guided discovery of mitogen-activated protein kinase 7 (MAPK7 inhibitors): integrating virtual screening, docking, and molecular dynamics simulations - Chandni Hayat; Amar Ajmal; Nayab Gul; Muhammad Numan; Haleema Bibi; Naveed Akhtar; Laiba Sultan; Arif Ali; Muhammad Tahir Khan; Muhammad Saqib (In Silico Pharmacology, 2026)

Cow, Buffalo and Goat Milk as a Pathway for Heavy Metal Exposure from Coal Mining Activities with Spatial and Species-Specific Health Risk Evaluation - Aima Iram Batool; Muhammad FayyazUrRehman; Javaria Ikram; Naima Huma Naveed; Hakim Bibi (Biological Trace Element Research, 2026)

Short dry period improves postpartum energy balance and reproduction but reduces milk yield in dairy cows - Melad Ahmed; Amjad Riaz; Nasim Ahmad; Muhammad Naveed ul Haque; Hifz ul Rahman; Muhammad Yaseen; Talha Ashraf; Muhammad Abdullah; Ali Hassan; Ali Husnain (Theriogenology, 2026)

Deciphering auxin-regulated stomatal development: Novel insights into phytochrome-interacting factors, FOUR LIPS, and SNF1-related kinase interactions - Abdul Wakeel Umar; Naveed Ahmad; Hamad Hussain; Muhammad Zeeshan; Ming Xu (Plant Science, 2026)

Beyond limitations: Integrating advanced analytical techniques for a new era of soil organic matter characterization - Adnan MUSTAFA; Qudsia SAEED; Lasisi H. TOBILOBA; Yakov KUZYAKOV; Muhammad NAVEED; Mohammad T.K. NEZHAD; Muhammed M. IBRAHIM; Jan FROUZ; Martin BRTNICKY; Jiri KUCERIK; Xiankai LU (Pedosphere, 2026)

Integration of mid and near-infrared spectroscopy for determining TPC and TFC in wheat varieties via multivariate analysis - Muhammad Zareef; Muhammad Arslan; Waqas Ahmad; Md Mehedi Hassan; Muhammad Naveed; Malik Muhammad Hashim; Sadaf Javaria; Quansheng Chen (Food Control, 2026)

Green Practices, knowledge processes and women’s business performance in Pakistan’s manufacturing sector - Said Muhammad; Yin Zhichao; Sajjad Alam; Naveed Khan (Environment, Development and Sustainability, 2025)

Performance comparison of complete mix reactor and static mixer in ballasted flocculation - Muhammad Qasim; Muhammad Naveed Afridi; Salman Ali Suhail; Usman Pervaiz Khan; Imtiaz Afzal Khan; Jong-Oh Kim (Chemosphere, 2025)

Amino acid functionalized graphene oxide nanocomposite with enhanced adsorption capacity towards methyl orange dye: Insights into kinetics and mechanism - Uzaira Jameel; Muhammad Naveed Qasim; Afnan Qabil Alshammari; Naseem Ahmad Khan; Muhammad Mateen; Behzodjon D. Mamatkodirov; Bakhtiyar T. Ibragimov; Xusheng Wang; Muhammad Nadeem Akhtar (Journal of Water Process Engineering, 2025)

Energy transport in ternary hybrid nanofluid with variable thermal conductivity under the combined effects of electroviscous, electric potential, and heat generation - Shafiq Ahmad; Aamir Abbas Khan; Muhammad Naveed Khan; Salah Knani; N. Ameer Ahammad; Ibrahim E. Elseesy (Dynamics of Atmospheres and Oceans, 2025)

Influence of Cattaneo-Christov radiative heat flux in magnetized flow performance of three different materials with variable constraints - Muhammad Yasir; Karim Choubani; Muhammad Naveed Khan; Mohammed A. Almeshaal; Mohamed Hussien (Dynamics of Atmospheres and Oceans, 2025)

Extraction of polysaccharides from waste medium as functional ingredients - Nan Zhao; Zhongyang Liu; Xinyue Fan; Muhammad Naveed Sheas; Xinyi Chen; Ting Yu; Fujie Yan (Bioresource Technology Reports, 2025)

Optimizing tree crown density of finite coastal vegetation patches for enhanced tsunami mitigation - Fakhar Muhammad Abbas; Ali Abdullah Zaid Aldrees; Sohail Iqbal; Amina; Muhammad Atiq Ur Rehman Tariq; Naveed Anjum; Mujahid Iqbal; Usman Ghani; Ghufran Ahmed Pasha (Natural Hazards, 2025)

Integrated Phosphorus Management and Bacillus Cereus MN54 Inoculation Improve Fodder Yield, Nutrient Use Efficiency and Economic Returns in Pearl Millet Grown in Calcareous Soils - Abdul Majeed; Qasim Ali; Muhammad Naveed; Mubshar Hussain (Journal of Soil Science and Plant Nutrition, 2025)

Retraction Note: Pharmacological support to anti-arthritic prospective of physostigmine: a new approach - Haseeb Ahsan; Ihtisham Haider; Muhammad Naveed Mushtaq; Muhammad Naeem Qaisar; Farwa Naqvi; Awais Asif (Inflammopharmacology, 2025)

Whole-Genome analysis of Bacillus subtilis MBBL2 genomic characterization and comparative genomics - Hajra Sohail; Muhammad Naveed; Tariq Aziz; Rania Ali El Hadi Mohamed; Fakhria A. Al-Joufi (Functional & Integrative Genomics, 2025)

Environmental pollution and green intergovernmental fiscal relations: Fiscal decentralization for sustainable governance - Fayaz Hussain Tunio; Zhao Rui Feng; Tayyab Raza Fraz; Muhammad Shahbaz; Naveed R. Khan; Shoh-Jakhon Khamdamov (Journal of Environmental Management, 2025)

Development of a Novel Composite Catalyst containing Renewable Biochar blended with Zinc Oxide and Copper Diphenyl Amine for Visible Light Photocatalytic Degradation of Methylene Blue - Muhammad Raashid; Muhammad Zain Akram; Mohsin Kazmi; Kashaf Imran; Amir Ikhlaq; Muhammad Bin Saeed; Naveed Ramzan; Zafar Masood (Water, Air, & Soil Pollution, 2025)

Assessing the effect of a yeast product (Pichia guilliermondii) on growth performance, carcass traits, gut morphology, intestinal microbial computation, and immune response in broilers - Noman Khurshid; Saima Naveed; Fazal Raziq; Muhammad Tahir Khan; Assad Ullah (Tropical Animal Health and Production, 2025)

Insights into genetic diversity and chlorpyrifos resistance in fall armyworm Spodoptera frugiperda (Smith) population of Pakistan - Afia Shafique; Muhammad Sarwar; Naima Razzaq; Naveed Akhtar Shad; Saba Akram; Rubab Zahra Naqvi; Muhammad Asif (Phytoparasitica, 2025)

Enhancing mechanical and durability properties of bentonite-modified self-compacting concrete - Khawaja Adeel Tariq; Aashir Waleed; Jamil Ahmad; Fahad Ali; Naveed Ahmad; Muhammad Danish Nisar (Innovative Infrastructure Solutions, 2025)

Toxic metal bioaccumulation and health-risk profiling in buffalo milk: a case study from coal mining areas of Chakwal, Pakistan - Aima Iram Batool; Javaria Ikram; Muhammad Fayyaz Ur Rehman; Naima Huma Naveed; Ifrah Zafar; Hakim Bibi (Environmental Geochemistry and Health, 2025)

Biofloc systems as a sustainable strategy to minimize heavy metal bioaccumulation in aquaculture - Ruhma Ihsan; Aima Iram Batool; Muhammad Fayyaz Ur Rehman; Javaria Ikram; Naima Huma Naveed; Iram Inayat; Syed Sikandar Habib (Aquaculture International, 2025)

Metabolite characterization of probiotic Enterococcus Faecium for targeting Salmonella Entrica gut bacteria causing gastroenteritis - Kashef Choudhary; Muhammad Naveed; Tariq Aziz; Syeda Izma Makhdoom; Muhammad Waseem; Nada K. Alharbi; Fatma Alshehri; Ashwag Shami; Maher S. Alwethaynani; Fahad Al-Asmari; Areej A. Alhhazmi; Fakhria A. Al-Joufi (Antonie van Leeuwenhoek, 2025)

Artificial neural network optimized green synthesis of cysteine-conjugated silver nanoparticles for antibacterial activity against staphylococcus nepalensis to combat cystitis - Muhammad Asim; Muhammad Naveed; Tariq Aziz; Maida Salah Ud Din; Fatma Alshehri; Ashwag Shami; Maher S. Alwethaynani; Deema Fallatah; Abeer M. Alghamdi; Fakhria A. Al-Joufi (Antonie van Leeuwenhoek, 2025)

Potential of Organic Amendments as a Sustainable Strategy to Enhance Rice Yield by Improving Nutrient Use Efficiency and Physiological Performance in Alkaline Soil - Muhammad Ahmed; Muhammad Tauseef Jaffar; Zulfiqar Ahmad; Muhammad Naveed; Syed Ayyaz Javed; Muhammad Shoaib Asad; Ali Raza; Awais Shakoor; Jianguo Zhang (Journal of Plant Growth Regulation, 2025)

Design and development of industrial prototype of spot specific orchard sprayer using ultrasonic sensing system and advanced pressure control mechanism - Arshed Ahmed; Shoaib Rashid Saleem; Muhammad Naveed Tahir; Shahram Hamza Manzoor; Qamar Zaman; Zhao Zhang; Rashed Ahmed (Computers and Electronics in Agriculture, 2025)

Xanthan gum coating delays ripening of harvested mango (Mangifera indica L.) fruit by suppressing chlorophyll catabolism and cell wall polysaccharides degradation - Maimona Qasim; Sajid Ali; Hafiz Umer Javed; Safina Naz; Ahmad Sattar Khan; Muhammad Hassan; Rana Naveed Ur Rehman (Postharvest Biology and Technology, 2025)

Optimizing the anticancer action and toxicity evaluation of cobalt ferrite nanoparticles by different polyethylene glycol concentrations - Kanwal Akhtar; Muhammad Khawar Abbas; Nida Muzammil; Naveed Akhtar Shad; Qaisar Iqbal; Wasim Abbas; Faqir Muhammad; Bushra Akhtar; Yasir Javed; Habiba Khadim; Anam Munawar (Journal of Trace Elements in Medicine and Biology, 2025)

Assessing the connectedness between green finance, financial developments, traditional energy consumption, economic growth, population aging and environmental degradation in RECP economies: A deep learning-based analysis - Hafiz Muhammad Naveed; Arshian Sharif; Muhammad Farhan Bashir; Mamdouh Abdulaziz Saleh Al-Faryan; Yanchun Pan (Journal of Environmental Management, 2025)

Corrigendum to “Designing highly potential photocatalytic comprising silver deposited ZnO NPs with sulfurized graphitic carbon nitride (Ag/ZnO/S-g-C3N4) ternary composite” [J. Environ. Chem. Eng. 9 (2021) 104919] - Shahid Iqbal; Naveed Ahmad; Mohsin Javed; Muhammad Azam Qamar; Ali Bahadur; Shahid Ali; Zahoor Ahmad; Rana Muhammad Irfan; Guocong Liu; Muhammad Bilal Akbar; Muhammad Abdul Qayyum (Journal of Environmental Chemical Engineering, 2025)

Microwave synthesis of rock-salt type high entropy oxides immobilized on graphene oxide nanosheets as an efficient catalyst for oxygen evolution reaction - Muhammad Asim; Akbar Hussain; Meryem Samancı; Ayşe Bayrakçeken; Andrea Straková Fedorková; Naveed Kausar Janjua (Journal of Environmental Chemical Engineering, 2025)

Efficacy and Safety of Mesenchymal Stromal Cells for Steroid-Refractory Acute Graft-versus-Host Disease: An Updated Meta-Analysis of Randomized Controlled Trials - Iftikhar Khan; Umama Rehman; Fatima Aslam; Saad Khan; Umna Bhatti; Hussain Ramzan; Fatima Naveed; Javeria Nawaz; Syeda Malaika Raza; Kiran Inam; Faiza Rajput; Syed Muhammad Seyab; et al. (Stem Cell Reviews and Reports, 2025)

Comparative Effects of Antibiotic and Antimicrobial Peptide on Growth Performance, Gut Morphology, Intestinal Lesion Score, Ileal Microbial Counts, and Immune Status in Broilers Challenged with Necrotic Enteritis - Muhammad Muneeb; Ehsaan Ullah Khan; Mubashar Ali; Muhammad Naveed Ul Haque; Muhammad Umar Zafar Khan; Sohail Ahmad (Probiotics and Antimicrobial Proteins, 2025)

Exogenic Application of Cinnamon Oil and Salicylic Acid Inhibits Alternaria Fruit Rot of Peach by Stimulating Defense-Related Enzymatic Activities - Sadia Hanif; Ambreen Maqsood; Muhammad Naveed Aslam; Muhammad Taimoor Shakeel; Atta ur Rehman; Mohammad Shafiq u Rahman; Shah Saud; Khaled Al-Kahtany; Shah Fahad (Journal of Plant Growth Regulation, 2025)

Legacy Polyfluoroalkyl Substances (PFAS) Contamination in Ravi and Sutlej Rivers, Punjab, Pakistan: Assessing Ecological and Human Health Risks - Naveed Akhtar; Asia Iqbal; Arshad Javid; Muhammad Tayyab (International Journal of Environmental Research, 2025)

Sphagnum microhabitats differentiate the nitrogen-fixing microbial communities in the Dajiuhu Peatland, central China: Significance of methane oxidation for nitrogen fixation - Liyuan Ma; Muhammad Naveed Nawaz; Ying Xu; Xiuyun Chen; Deng Liu; Xiaolu Lu; Hongmei Wang (Applied Soil Ecology, 2025)

Molecular characterization and green synthesis of iron oxide nanoparticles from Ureibacillus chungkukjangi for methylene blue degradation - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Shumaila Ibrahim; Maida Salah Ud Din; Maryam M. Alomran; Ashwag Shami; Fakhria A. Al-Joufi; Ahmad A. Alghamdi; Abdullah A. Alqasem; Ahmed M. Basri; Majid Alhomrani (Antonie van Leeuwenhoek, 2025)

Molecular Simulation and Expression Analysis of Vitamin C and Curcumin in Mitigating Buprofezin-induced Genotoxicity and Inflammatory Responses in Balb/c Mice - Haleema Sadia; Irfan Zia Qureshi; Muhammad Naveed; Tariq Aziz; Manal F. Elkhadragy; Maher S. Alwethaynani; Fahad Al-Asmari; Areej A Alhhazmi; Hanan Abdulrahman Sagini; Suad Hamdan Almasoudi; Fakhria A. Al-Joufi (Cell Biochemistry and Biophysics, 2025)

Dinaphthodiospyrol H: a natural α-glucosidase inhibibitor extracted from Diospyros kaki L.f - Abdur Rauf; Taghrid S. AlOmar; Umer Rashid; Zubair Ahmad; Sofia Kanwal; Najla Almasoud; Naveed Muhammad; Margrate Anyanwu; Alessandra Gianoncelli; Giovanni Ribaudo (Natural Product Research, 2025)

Effect of Bioactive Peptides and Encapsulated Butyric Acid on Growth Performance, Gut Health, Immune Status and Nutrient Digestibility in Broiler Chickens - Mohammad Ahmad Qazi; Ehsaan Ullah Khan; Saima Naveed; Shahid Mehmood; Muhammad Muneeb; Muhammad Talha; Muhammad Shabir Shaheen; Sohail Ahmad (International Journal of Peptide Research and Therapeutics, 2025)

Retraction notice to “Comparative study of ozonation and ozonation catalyzed by Fe-loaded biochar as catalyst to remove methylene blue from aqueous solution” [Chemosphere 307 Part 1, November 2022, 135738] - Muhammad Babar; Hafiz Muhammad Shahzad Munir; Aamna Nawaz; Naveed Ramzan; Umair Azhar; Muhammad Sagir; Muhammad Suleman Tahir; Amir Ikhlaq; Siti Nuurul huda Mohammad Azmin; Muhammad Mubashir; Kuan Shiong Khoo; Kit Wayne Chew (Chemosphere, 2025)

Structural and functional insights into Jasmonate ZIM-domain 2 (GhJAZ2) interactions in cotton fiber development via Jasmonic acid signaling - Muhammad Sulyman Saleem; Sultan Habibullah Khan; Zunaira Afzal Naveed (Plant Gene, 2025)

A cross cultural study: Financial freedom nexus with green development - Muhammad Naveed Jamil; Abdul Rasheed (Journal of Cleaner Production, 2025)

Advancing algae-based Bioenergy: Techno-Economic assessment of hydrogen and biochar production from algal biomass - Aliyan Tanweer; Syed Ali Ammar Taqvi; Bilal Kazmi; Safiya Khatoon; Muhammad Taha; Muhammad Nadir; Farooq Ahmad; Naveed Ahmad (Biomass and Bioenergy, 2025)

Crop Residue Management for Soil Health and Environmental Sustainability: A Comprehensive Review - Sadia Babar Baloch; Shahzaib Ali; Jaroslav Bernas; Petr Konvalina; Muhammad Naveed; Faryal Babar Baloch; Zameer Hussain Jamali; Tomáš Lošák; Hynek Roubík; Abdul Ghafoor; Mohsin Mehmood; Adnan Mustafa (Journal of Soil Science and Plant Nutrition, 2025)

Soil C/P Stoichiometry Mediated Microbially Driven Phosphorus Mobilization: New Insight in Soil P Management - Khuram Shehzad Khan; Muhammad Naveed; Allah Ditta; Tajwar Alam; Muhammad Zahid Mumtaz; Aown Abbas; Lingling Li (Journal of Soil Science and Plant Nutrition, 2025)

Unlocking the Geoheritage Potential of Hingol National Park (HNP), Pakistan: Geological and Geomorphological Insights Through Multi-Satellite Remote Sensing Data and Field Geology Validation - Muhammad Yaseen; Rujun Chen; Jawad Ahmad; Shahid Ali Shah; Shah Fahad; Muhammad Naveed Anjum; Syed Tanvir Shah (Geoheritage, 2025)

Survey and seasonal abundances of major insect pest species in the maize fields of Punjab, Pakistan - Naveed Akhtar; Hafiz Muhammad Tahir; Azizullah; Aamir Ali; Rabia Fajar; Ayesha Muzamil; Reham Fathy; Hend O. Mohamed; Dilawar Abbas (International Journal of Tropical Insect Science, 2025)

Correction to: Transition metal-doped SnO2 and graphene oxide (GO) supported nanocomposites as efficient photocatalysts and antibacterial agents - Tauseef Munawar; Muhammad Shahid Nadeem; Faisal Mukhtar; Muhammad Naveed ur Rehman; Muhammad Riaz; Sana Batool; Murtaza Hasan; Faisal Iqbal (Environmental Science and Pollution Research, 2025)

Boosted wound healing and anticancer potential of polymer functionalized cerium oxide nanomaterials - Muhammad Khawar Abbas; Yasir Javed; Naveed Akhtar Shad; Azhar Rasul; Amna Bashir; Syed Fazil Bin Farukh; Heba Taha Abdulghani; Wasim Abbas; Aisha Sethi; Muhammad Ramzan Khawar; Dongwhi Choi (Journal of Trace Elements in Medicine and Biology, 2025)

Soil texture-driven modulation of poly-3-hydroxybutyrate (P3HB) biodegradation: Microbial shifts, and trade-offs between nutrient availability and lettuce growth - Martin Brtnicky; Adnan Mustafa; Jiri Holatko; Anna Gunina; Gabrijel Ondrasek; Muhammad Naveed; Tereza Hammerschmiedt; Eliska Kamenikova; Saud Alamri; Manzer H. Siddiqui; Antonin Kintl; Tivadar Baltazar; et al. (Environmental Research, 2025)

Machine learning assisted predictive urban digital twin for intelligent monitoring of air quality index for smart city environment - Khazina Naveed; Tariq Umer; Aamer Bilal Asghar; Muhammad Aslam; Krzysztof Ejsmont; Ahmed Sayed Mohammed Metwally; Kien Nguyen Thanh (Environmental Modelling & Software, 2025)

Genotypic Profiling, Functional Analysis, Cholesterol-Lowering Ability, and Angiotensin I-Converting Enzyme (ACE) Inhibitory Activity of Probiotic Lactiplantibacillus plantarum K25 via Different Approaches - Tariq Aziz; Hu Hangyu; Muhammad Naveed; Muhammad Aqib Shabbir; Abid Sarwar; Jasra Nasbeeb; Yang Zhennai; Metab Alharbi (Probiotics and Antimicrobial Proteins, 2025)

Efficacy of Flumetsulam for Post-Emergence Weed Management in Chickpea (Cicer Arietinum L.) Under the Semi-Arid Region of Pakistan - Muhammad Khuram Razzaq; Ali Aziz; Faisal Hayat; Muhammad Zia Ul Haq; Irfan Rasool; Muhammad Naveed Babur; Ali Aslam; Sher Muhammad; Ammara Tahir; Khalid Hussain (Journal of Crop Health, 2025)

Tegoprazan: a novel, highly selective, and potent potassium-competitive acid blocker (P-CAB) - Wenlu Wang; Hafiza Sidra Yaseen; Xiaoji Li; Muhammad Zia Ahmad; Yaowu Chen; Guorong Li; Muhammad Naveed; Hafiz Muhammad Zubair; Jannat Bibi (European Journal of Clinical Pharmacology, 2025)

Exploring the antitumor effects of Pd(II) complexes with nitrogen donor ligands towards breast carcinoma - Shazia Hussain; Sara Masood; Shabeeb Hussain; Irfan Hussain; Fouzia Malik; Muhammad Nadeem Akhtar; M. Naveed Zafar (BioMetals, 2025)

Gum Arabic Organic Coating Maintains Freshness and Modulates Oxidative Stress by Augmenting the Antioxidant Activities of Harvested Ber Fruit - Alisha Noor; Ahmad Sattar Khan; Raheel Anwar; Sajid Ali; Rana Naveed Ur Rehman; Saqib Ayyub; Muhammad Haider Ali (Applied Fruit Science, 2025)

Challenges and Strategies in Managing Naegleria fowleri-Associated Primary Amoebic Meningoencephalitis in Pakistan: A Case Report - Maham Zaman; Tooba Fida; Hafiz Muhammad Haris; Zarmeen Naveed; Shaheer Haider; Tauqeer Khan (Acta Parasitologica, 2025)

Salicylic acid-induced defense responses against a newly identified cotton pathogen, Pantoea vagans - Muneeb Anwer; Muhammad Waqas Azam; Muhammad Taimoor Shakeel; Anam Moosa; Hongwei Zhao; Muhammad Aslam Farooqi; Mahmoud Moustafa; Mohammed O. Alshaharni; Uthman Algopishi; Huda Alghamdi; Ambreen Maqsood; Muhammad Naveed Aslam (Physiological and Molecular Plant Pathology, 2025)

Breakthrough in plasmonic enhanced MOFs: Design, synthesis, and catalytic mechanisms for various photocatalytic applications - Waqar Ahmad Qureshi; Syed Najeeb-Uz-Zaman Haider; Muhammad Adnan Qaiser; Shahid Khan; Weikang Wang; Rai Nauman Ali; Amjad Ali; Ahmad Naveed; Mohamed Hussein Abdurahman; Muhammad Usman Khan; Muhammad Tayyab; Lele Wang; et al. (Environmental Research, 2025)

Preparation, Characterization and Removal of Acid Blue 129 and Erioglaucine Dyes from Aqueous Solution by Corn Cob Based Activated Carbon - Sultan Alam; Najeeb ur Rahman; Muhammad Ilyas; Iram --; AlSaba Gul; Muhammad Zahoor; Muhammad Naveed Umar; Riaz Ullah; Essam A. Ali (Bulletin of Environmental Contamination and Toxicology, 2025)

Towards sustainable methanol production: energy, exergy, economics, and environmental evaluation of Thar coal gasification - Syeda Asra Arshad; Umna Nasir Ali; Syed Ali Ammar Taqvi; Bilal Kazmi; Ahsan Khalid; Muhammad Ahmer; Farooq Ahmad; Naveed Ahmad (Environment, Development and Sustainability, 2025)

Engineering innovative catalysts for efficient CO2 reduction toward carbon neutrality - Muhammad Awais; Naveed Ashraf; Younes Abghoui (Journal of Environmental Chemical Engineering, 2025)

Modeling earthquake-induced seiche processes and subsequent homogenite deposition in lacustrine settings - Muhammad Naveed Zafar; Pierre Sabatier; Denys Dutykh; Hervé Jomard; William Rapuc; Patrick Lajeunesse; Emmanuel Chapron (Earth and Planetary Science Letters, 2025)

Effect of Phosphorus Modified Cotton Stick Biochar on Growth, Photosynthesis, Enzymatic Activities and Lead (Pb) Uptake in Tomato Plants Grown in Pb-contaminated Soil - Zaffar Malik; Aleena Shabir; Ahmad Ali; Muhammad Naveed Aslam; Humera Aziz; Syed Farhan Haider Bukhari; Sana Noreen; Usama Ali Tahir; Muhammad Rizwan (Journal of Soil Science and Plant Nutrition, 2025)

Inheritance of Cell Membrane Stability and Yield Components Under Drought and Salinity Stress in Bread Wheat (Triticum aestivum L.) - Sameena Naqi; Aamir Hamid Khan; Rashid Mehmood Rana; Muhammad Imran Hamza; Marcin Kiedrzyński; Muhammad Naveed Tahir; Munir Ahmad; Shah Saud; Shah Hassan; Shah Fahad (Journal of Plant Growth Regulation, 2025)

Relative change in accommodation space and sedimentation rates of Jurassic to Middle Eocene sedimentary facies in the NW Himalaya, Pakistan - Tariq Mahmood; Naveed Ahsan; Muhammad Armaghan Faisal Miraj; Shaukat Ali; Faisal Shah; Syed Kamran Ali (Carbonates and Evaporites, 2025)

Effect of Diagenetic Processes and Depositional Facies on Reservoir Quality of the Eocene Carbonate Sequence (Sakesar Limestone) in the Central Salt Range, Pakistan - Naveed Rehman; Shu Jiang; Syed Haroon Ali; Asim Falak Naz; Muhammad Tariq (Journal of Earth Science, 2025)

Prospecting high-altitude springs in the Upper Indus Basin, Pakistan: Knowledge towards policy development - Arshad Ashraf; Muhammad Bilal Iqbal; Ali Kamran; Naveed Mustafa (Groundwater for Sustainable Development, 2025)

Exploring the potential of a pH-sensitive hydrogel sponge: interpenetrating network of tragacanth and pectin for controlled delivery of levosulpiride - Muhammad Umer Ashraf; Muhammad Awais Iqbal; Kashif Barkat; Irfan Anjum; Muhammad Naveed Mushtaq; Rabia Gul; Muhammad Aamir; Samir Ibenmoussa; Ahmad Mohammad Salamatullah; Mohammed Bourhia; Gamal A. Shazly; Gezahign Fentahun Wondmie (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Rice grain size: current regulatory mechanisms and future perspectives - Muhammad Yaseen; Naveed Tariq; Rida Kanwal; Akasha Farooq; Hao Wang; Hua Yuan (Journal of Plant Research, 2025)

Morpho-physiological attributes, antioxidant activities, proximate seed analysis, and phytoremediative prospective of two castor bean genotypes in lead spiked soil - Sahar Naveed; Sajid Mahmood; Wajid Ishaque; Muhammad Akhtar (Acta Physiologiae Plantarum, 2025)

Polycyclic aromatic hydrocarbons (PAHs) occurrences in water bodies, extraction techniques, detection methods, and standardized guidelines for PAHs in aqueous solutions - Rana Muhammad Mubeen Muhsin; Teh Sabariah Binti Abd Manan; Joseph Bidai; Muhammad Sarfraz Ahmad Mangat; Zarimah Mohd Hanafiah; Adel Gohari; Naveed Ahmad; Farooq Ahmad; Salmia Beddu; Nur Liyana Mohd Kamal; Daud Mohamad; Shatha Aser Hamad Aldala'in; et al. (Science of The Total Environment, 2025)

Starvation from within: How heavy metals compete with essential nutrients, disrupt metabolism, and impair plant growth - Abdul Wakeel Umar; Muhammad Naeem; Hamad Hussain; Naveed Ahmad; Ming Xu (Plant Science, 2025)

Boosted proton conduction in LAO electrolyte through Li segregation for High-Performance ceramic fuel cells - Nabeela Akbar; Muhammad Yousaf; M.A.K. Yousaf Shah; Jahangeer Ahmed; Asma Noor; Quazi Arif Islam; Yan Wu; Saad M. Alshehri; Naveed Mushtaq; Bin Zhu; Sara Paydar (Fuel, 2025)

Fish oil replacement with linseed oil affects growth, tissue fatty acid composition, blood chemistry, and antioxidant biomarkers in rohu, Labeo rohita - Muhammad Asghar; Noor Khan; Mahroze Fatima; Seyda Tacer-Tanas; Simon John Davies; Naveed ul Haque; Ayesha Tanveer; Murat Arslan (Aquaculture International, 2025)

Potential role of inoculum size in biomass accumulation and antioxidant secondary metabolites production in adventitious root cultures of Stevia rebaudiana - Naveed Ahmad; Nisar Ahmad; Muhammad Sajid; Kamran Rauf; Mudassar Iqbal; Muhammad Numan; Irfan Ullah; Amir Khan; Wahidah H. Al-Qahtani; Mostafa A. Abdel-Maksoud; Hamada AbdElgawad; Babar Iqbal; et al. (Plant Biosystems, 2025)

Molecular phylogeny and cryptic species identification of the genus Triplophysa in the freshwater of Malakand division, Pakistan - Omer dad; Muhammad Fiaz Khan; Akhtar Rasool; Mohammad Attaullah; Muhammad Israr; Naveed Akhtar (Zoologischer Anzeiger, 2025)

First report of leaf spot of Wodyetia bifurcata caused by Alternaria alternata in Pakistan - Muhammad Abu Bakar; Roshaan Ahmed; Ambreen Maqsood; Muhammad Naveed Aslam; Muhammad Taimoor Shakeel (Physiological and Molecular Plant Pathology, 2025)

Impacts of soiling on solar panel performance and state-of-the-art effective cleaning methods: A recent review - Nadia Shahzad; Naveed Hussain; Shayan Umar; Muhammad Farooq Azam; Tanzeela Yousaf; Adeel Waqas (Journal of Cleaner Production, 2025)

Unveiling exceptional conduction mechanism and high proton conductivity in amorphous electrolyte for advanced ceramic fuel cells - Touseef Ahmad; Naveed Mushtaq; Hafsa Mansha; Kashf Zaman; Muhammad Khalid; Muhammad Ahsan Masood; Muhammad Shahid Sharif; Yuzheng Lu; Bin Zhu (Fuel, 2025)

Unveiling the future: Breakthroughs and innovations in MXene-based electrochemical sensors - Muhammad Khan; Xiaohui Sun; Faisal Attique; Muhammad Tahir Saleh; Naveed Ahmad; Kainat Atiq; Muhammad Shafi; Inas A. Ahmed; Imad Barsoum; Muhammad Shahbaz Rafique; Azeem Ullah; Amjad Hussain; et al. (Chemical Engineering Journal, 2025)

Visible light active CdS/CuO nanocomposites for photocatalytic degradation of ciprofloxacin, H2 production and antimicrobial activity - Naveed Akhtar; Chaejin Choi; Muhammad Ateeq; Perveen Fazil; Noor S. Shah; Javed Ali Khan; Abdullah G. Al-Sehemi; Amir Zada; Muhammad Ishaq Ali Shah; Rabia Ikram; Changseok Han (Chemical Engineering Journal, 2025)

Proteomic insights into fruit–pathogen interactions: managing biotic stress in fruit - Aidhya Irhash Putra; Muhammad Naveed Khan; Nurhaida Kamaruddin; Raja Farhana R. Khairuddin; Jameel R. Al-Obaidi; Brenda Juana Flores; Luis Fernando Flores (Plant Cell Reports, 2025)

Thymol as a Novel Plant-Derived Antibacterial Agent for Suppressing Xanthomonas citri pv. malvacearum in Cotton - Muhammad Naveed Aslam; Huma Khaliq; Hongwei Zhao; Anam Moosa; Ambreen Maqsood; Muhammad Aslam Farooqi; Muhammad Saqib Bilal; Tahir Mahmood; Tariq Mukhtar (Current Microbiology, 2025)

The efficacy of egg albumin nanoparticles adjuvanted Clostridium perfringens type D toxoid vaccine in rabbits - Mehwish Saeed; Saad Zafar; Zarreen Sajjad; Rizwan Aslam; Sultan Ali; Muhammad Shahid Mahmood; Mueed Aayan; Maria Sophy; Saqib Umer; Sajjad Ur Rahman; Muhammad Naveed Anwar (Brazilian Journal of Microbiology, 2025)

Effects of dietary organic selenium, vitamin C, and vitamin E supplementation on growth performance, serum biochemistry, and antioxidant status in juvenile Hypophthalmichthys molitrix - Hairui Yu; Maida Mushtaq; Saira Razzaq; Umar Ali; Muhammad Khan; Abdur Rahman; Guobo Quan; Mehroze Fatima; Saima Naveed; Muhammad Hammad Zafar; Muhammad Aziz ur Rahman (Frontiers in Marine Science, 2025)
The study aimed to evaluate the effects of dietary supplementation of selenium (Se), vitamin C, and vitamin E on growth performance, meat quality, and antioxidant status in Hypophthalmichthys molitrix juveniles. A total of 480 juveniles (mean weight: 20 ± 0.29 g) were randomly assigned to 24 aquaria (20 fish per 100 L), which were allocated to eight dietary treatments (three aquaria per treatment) following a completely randomized design. The dietary treatments included: (1) a basal diet without supplementation (Control), (2) selenium supplementation (S), (3) vitamin C supplementation (C), (4) vitamin E supplementation (E), (5) selenium and vitamin C supplementation (SC), (6) selenium and vitamin E supplementation (SE), (7) vitamin C and vitamin E supplementation (EC), and (8) selenium, vitamin C, and vitamin E supplementation (SCE). The supplementation levels were 0.9 mg/kg Se, 300 mg/kg vitamin C, and 100 mg/kg vitamin E, respectively. After a one-week acclimatization period, a 10-week growth trial was conducted. Fish fed the SCE diet exhibited significantly higher (p< 0.05) final weight gain, body length gain, body weight gain percentage, and specific growth rates compared to other treatments. Selenium concentrations in the kidney, liver, pancreas, and muscle were significantly higher (p< 0.05) in the SCE, SC, SE, and EC groups compared to the Control and single-supplement groups. Hematological parameters, including WBC, RBC, HGB, HCT, and MCHC, were significantly higher (p< 0.05) in the SCE group compared to all other groups. Similarly, serum activities of ALT, AST, and ALP were significantly lower (p< 0.05) in the SCE group than in other treatments, while blood glucose levels were unaffected (p > 0.05) by dietary treatments. Antioxidant enzyme activities, including superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx), were significantly enhanced (p< 0.05) in the whole body and muscle tissues of fish receiving Se, vitamin C, and E supplementation. Thiobarbituric acid reactive substances (TBARS) levels in muscle and serum were significantly higher (p< 0.05) in the Control group compared to all supplemented groups. The proximate composition of meat, including dry matter, fat, ash, and protein contents, was not significantly affected (p > 0.05) by the dietary treatments. In conclusion, dietary supplementation of selenium, vitamin C, and vitamin E significantly improved growth performance, selenium deposition in tissues, and antioxidant status of Hypophthalmichthys molitrix juveniles, without adversely affecting meat chemical composition.

Identification and quantification of selected heavy metals by ICP-OES in skin whitening creams marketed in Pakistan - Mirza Nadeem Ahmad; Umm-e-Khadija Ashraf; Muhammad Naveed Anjum; Shumaila Kiran; Shazia Abrar; Muhammad Fayyaz Farid (Environmental Monitoring and Assessment, 2025)

Exploring the phytochemical profile, antioxidant activity, and anticancer potential of Achillea millefolium extracts: In-vitro and in-silico investigation - Asia Kiran; Awais Altaf; Muhammad Sarwar; Tahir Maqbool; Muhammad Abdul Basit Ashraf; Muhammad Naveed; Tariq Aziz; Metab Alharbi (South African Journal of Botany, 2025)

In-vitro and in-vivo assessments of greenly synthesized iron oxide nanoparticles from Cascabela thevetia plant extract for the treatment of ventricular septal defect - Amina Abid; Muhammad Naveed; Tariq Aziz; Muhammad Aqib Shabbir; Hira Mubeen; Ayaz Ali Khan; Abdullah F Alsmari (South African Journal of Botany, 2025)

The induction of polyamines metabolism pathway and membrane stability with silicon alleviate the vanadium toxicity in pepper plants - Naveed Mushtaq; Muhammad Ahsan Altaf; Huangying Shu; Xu Lu; Shanhan Cheng; Mohamed A. El-Sheikh; Parvaiz Ahmad; Huizhen Fu; Zhiwei Wang (Journal of Hazardous Materials, 2025)

Addressing dye phytotoxicity and soil contamination: The dual action of chemically synthesized zinc nanoparticles in simultaneous adsorption and soil health improvement - Zainab Naseem; Muhammad Naveed; Saher Nawaz; Raafia Anam Saeed; Manzer H. Siddiqui; Adnan Mustafa; Avelino Núñez-Delgado (Journal of Environmental Management, 2025)

Catalytic charge synergy on Ni/Sr@rTiO2 system to promote hydrogen evolution for the implementation of green energy technologies - Ejaz Hussain; Sidra Khan; Muhammad Jalil; Muhammad Zeeshan Abid; Abdul Rauf; Nagina Naveed Riaz; Abeer Hashem; Ajay Kumar; Elsayed Fathi Abd_Allah; Khezina Rafiq (Fuel, 2025)

Surface Water Analysis for Physical Parameters, Fecal Indicator Bacteria, and Identification of the Origin of Contamination - Sadaf Tagar; Naveed Ahmed Qambrani; Zubair Ahmed; Kamran Ansari; Rasool Bux Mahar; Muhammad Muqeet; Syed Muhammad Zaki Zaidi (Water, Air, & Soil Pollution, 2025)

Disease resistance to tomato yellow leaf curl virus (TYLCV) enhanced by natural plant growth regulators and biopesticide - Sajid Mehmood; Marina Sajid; Tamsal Murtaza; Tanveer Hussain; Rana Naveed Ur Rehman; Muhammad Tahir Akram; Huma Abbas; Khadija Rafiq; Muhammad Kamran; Manzoor Hussain; Muhammad Inam ul Haq; Gull-e-laala Khan (Journal of Plant Diseases and Protection, 2025)

Prevalence and genetic diversity of potato virus Y strains in Pakistani potato fields: insights from partial sequence analysis - Muhammad Hamza Shahid; Ghulam Mustafa Sahi; Zunaira Afzal Naveed; Safdar Ali; Muhammad Wahab; Muhammad Sagheer; Azher Mustafa (Journal of Plant Diseases and Protection, 2025)

Retraction Note: The integrin facilitated internalization of fibronectin-functionalized camptothecin-loaded DNA-nanofibers for high-efficiency anticancer effects - Mirza Muhammad Faran Ashraf Baig; Wing-Fu Lai; Saba Ashraf; Ammara Saleem; Muhammad Furqan Akhtar; Reyaj Mikrani; Muhammad Naveed; Farhan Siddique; Abdoh Taleb; Jahanzeb Mudassir; Ghulam Jilany Khan; Muhammad Tayyab Ansari (Drug Delivery and Translational Research, 2025)

Synergistic electrochemical performance of textile sludge based activated carbon with reduced graphene oxide as electrode for supercapacitor application - Naveed Ahmed Khan; Zaib Jahan; Naseem Iqbal; Muhammad Bilal Niazi; Rimsha Mehek (Waste Management, 2025)

Photocatalytic degradation of Congo red using RGO-modified MIL-125(Ti) under visible light - Rida Fatima; Muhammad Naveed Afridi; Idriss Mohdeb; Puttaswamy Madhusudan; Yuhoon Hwang (Journal of Water Process Engineering, 2025)

High-Entropy Li-doped rock salt catalyst for low-Temperature ceramic fuel cells - Muhammad Khalid; M.A.K. Yousaf Shah; Nabeela Akbar; Naveed Mushtaq; Rizwan Raza; Jun Wang; Bin Zhu (Fuel, 2025)

Combined pharmacological and computational approaches unraveling the protective effects of Cassia angustifolia extract against NANO2 - induced neurodegeneration and hepatotoxicity - Shabina Ishtiaq Ahmed; Humaira Ismatullah; Qaisar Mansoor; Muhammad Yaseen; Aisha Naveed; Muhammad Qasim Hayat; Saadia Zahid; Junaid Arshad; Mubarra Tahir; Mashooq Ahmad Bhat (Food Bioscience, 2025)

Microwave-assisted, sulfhydryl-modified β-cyclodextrin-silymarin inclusion complex: A diverse approach to improve oral drug bioavailability via enhanced mucoadhesion and permeation - Shumaila Arshad; Syed Atif Raza; Alamgeer; Syed Nasir Abbas Bukhari; Nasser F. Alotaibi; Naveed Ahmad; Hafiz Muhammad Irfan; Arshad Mahmood; Mulazim Hussain Asim (Carbohydrate Polymers, 2025)

Climate change projections for Diamer Division in lesser Himalayas using multi-global climate model ensemble - Didar Ahmad; Faridullah Faridullah; Muhammad Irshad; Aziz Ur Rahim Bacha; Farhan Hafeez; Akhtar Iqbal; Zahid Ullah; Muhammad Naveed Afridi; Abdulwahed Fahad Alrefaei; Rashid Nazir (Environmental Science and Pollution Research, 2024)

Systematic review on buparvaquone resistance associated with non-synonymous mutation in drug binding genes site of Theileria annulate - Muhammad Rashid; Muhammad Hassan Hayat; Naveed Zahra; Mian Sayed Khan; Suleman; Muhammad Nadeem; Tauseef ur Rehman; Muhammad Ehsan; Muhammad Irfan Malik; Muhammad Kashif Obaid; Amir Bakhsh; Mohamed Aziz Darghouth; et al. (Veterinary Parasitology, 2024)

Characterization of mercury ameliorating rhizobacteria for enhancing growth and yield of Triticum aestivum L. in the field: An in-vitro and in- silico study - Aatif Amin; Muhammad Naveed; Sunbul Rasheed; Zakia Latif; Tariq Aziz; Fahad Al Asmari; Maha Aljabri (South African Journal of Botany, 2024)

Unlocking plant resilience: Advanced epigenetic strategies against heavy metal and metalloid stress - Babar Iqbal; Naveed Ahmad; Guanlin Li; Arshad Jalal; Ali Raza Khan; Xiaojun Zheng; Muhammad Naeem; Daolin Du (Plant Science, 2024)

Kinetics of silver ion encapsulation as nanoparticles using Vaccinium oxycoccos plant extract for the efficient sensing of Cr(iii) ions and its biological assessment - Amna Bibi; Muhammad Iqbal Zaman; Abdul Niaz; Sania Bibi; Saba Gul; Naveed Ahmad; Hanan E. Osman (Chemical Engineering Journal, 2024)

Interactive effects of melatonin and salicylic acid on Brassica napus under drought condition - Noman Rafique; Noshin Ilyas; Muhammad Aqeel; Naveed Iqbal Raja; Ghulam Shabbir; Muhammad Ajaib; R. Z. Sayyed; Sulaiman Ali Alharbi; Mohammad Javed Ansari (Plant and Soil, 2024)

Nitrogen and carbohydrate metabolisms are key factors in maize (Zea mays L.) germination under chromium-induced ROS - Muhammad Imran Atta; Syeda Sadaf Zehra; Zhihang Zhuo; Habib Ali; Malik Waseem Abbas; Syed Naveed Abbas; Sadia Sarwar; Fatima Muneer; Irfan Ahmad; Danpping Xu; Hasham S. Almoallim; Mohammad Javed Ansari (Journal of Plant Diseases and Protection, 2024)

Artificial Intelligence-Based Classification of CT Images Using a Hybrid SpinalZFNet - Faiqa Maqsood; Wang Zhenfei; Muhammad Mumtaz Ali; Baozhi Qiu; Naveed Ur Rehman; Fahad Sabah; Tahir Mahmood; Irfanud Din; Raheem Sarwar (Interdisciplinary Sciences: Computational Life Sciences, 2024)
The kidney is an abdominal organ in the human body that supports filtering excess water and waste from the blood. Kidney diseases generally occur due to changes in certain supplements, medical conditions, obesity, and diet, which causes kidney function and ultimately leads to complications such as chronic kidney disease, kidney failure, and other renal disorders. Combining patient metadata with computed tomography (CT) images is essential to accurately and timely diagnosing such complications. Deep Neural Networks (DNNs) have transformed medical fields by providing high accuracy in complex tasks. However, the high computational cost of these models is a significant challenge, particularly in real-time applications. This paper proposed SpinalZFNet, a hybrid deep learning approach that integrates the architectural strengths of Spinal Network (SpinalNet) with the feature extraction capabilities of Zeiler and Fergus Network (ZFNet) to classify kidney disease accurately using CT images. This unique combination enhanced feature analysis, significantly improving classification accuracy while reducing the computational overhead. At first, the acquired CT images are pre-processed using a median filter, and the pre-processed image is segmented using Efficient Neural Network (ENet). Later, the images are augmented, and different features are extracted from the augmented CT images. The extracted features finally classify the kidney disease into normal, tumor, cyst, and stone using the proposed SpinalZFNet model. The SpinalZFNet outperformed other models, with 99.9% sensitivity, 99.5% specificity, precision 99.6%, 99.8% accuracy, and 99.7% F1-Score in classifying kidney disease. Graphical Abstract

Characterization and Quantification of Outcrops Exposed Along the Karakoram Highway (KKH) and Part of Central Karakoram National Park (CKNP), North Pakistan; Implications for Geoheritage Assessments and Geosite Recognition - Muhammad Yaseen; Jawad Ahmad; Muhammad Naveed Anjum; Abbas Ali Naseem; Syed Tanvir Shah (Geoheritage, 2024)

Correction: Determination of Toxic Elements in Cannabinoid and Opioid Drugs and Their Impact on Addicts’ Health: A Comparative Study - Ahsanullah Unar; Oan Muhammad Sahito; Laila Alsawalha; Hassan Imran Afridi; Farid Shokry Ataya; Muhammad Sohail Bashir; Dalia Fouad; Farah Naz Talpur; Naveed Ali (Biological Trace Element Research, 2024)

Determination of Toxic Elements in Cannabinoid and Opioid Drugs and Their Impact on Addicts’ Health: A Comparative Study - Ahsanullah Unar; Oan Muhammad Sahito; Laila Alsawalha; Hassan Imran Afridi; Farid Shokry Ataya; Muhammad Sohail Bashir; Dalia Fouad; Farah Naz Talpur; Naveed Ali (Biological Trace Element Research, 2024)

Nutritional composition assessment and antimicrobial activity of Catostylus perezi , jellyfish blooms along the coast of Pakistan: an awareness to avoid food neophobia in Pakistan - Muhammad Naveed; Malik Wajid Hussain Chan; Sadar Aslam; Fenghuan Wang; Anas Sajjad; Asad Ullah; Nida Saleem; Muhammad Samee Haider; Victoria Arija (Natural Product Research, 2024)

Enhanced cadmium immobilization in soil using Fe- and Zn-doped biochar: Mechanisms and safety implications for Cicer arietinum L - Uzma Muzaffar; Muhammad Naveed; Zainab Naseem; Iqra Abid; Kashif Zulfiqar Amir; Saud Alamri; Muhammad Siddique; Martin Brtnicky; Adnan Mustafa (Chemosphere, 2024)

Diagenesis and reservoir quality evolution of estuarine sandstones: Insights from the Cenomanian-Turonian Yolde Formation, northern Benue Trough, NE Nigeria - Abdulwahab M. Bello; Musa B. Usman; Abduljamiu O. Amao; Khalid Al-Ramadan; Murtada Al-Hashem; Aliyuda Kachalla; Usman Abubakar; Anas M. Salisu; Shehu Mukkafa; Ibrahim A. Kwami; Oluwafemi E. Aro; Muhammad Naveed Butt; et al. (Marine and Petroleum Geology, 2024)

Proximate composition and prevalence and exposure assessment of aflatoxins intake through consumption of fresh carrot and processed marketed carrot products in South Punjab, Pakistan - Aneela Nijabat; Shahwana Bibi; Maryam Ajmal; Saher Nawaz; Muhammad Zaheer Sajid; Saad Ullah Khan Leghari; Muhammad Mahmood-ur-Rehman; Naima Huma Naveed; Aamir Ali; Philipp W. Simon (Natural Product Research, 2024)

Rare homozygous cilia gene variants identified in consanguineous congenital heart disease patients - Daniel A. Baird; Hira Mubeen; Canan Doganli; Jasmijn B. Miltenburg; Oskar Kaaber Thomsen; Zafar Ali; Tahir Naveed; Asif ur Rehman; Shahid Mahmood Baig; Søren Tvorup Christensen; Muhammad Farooq; Lars Allan Larsen (Human Genetics, 2024)
Congenital heart defects (CHD) appear in almost one percent of live births. Asian countries have the highest birth prevalence of CHD in the world. Recessive genotypes may represent a CHD risk factor in Asian populations with a high degree of consanguineous marriages. Genetic analysis of consanguineous families may represent a relatively unexplored source for investigating CHD etiology. To obtain insight into the contribution of recessive genotypes in CHD we analysed a cohort of forty-nine Pakistani CHD probands, originating from consanguineous unions. The majority (82%) of patient’s malformations were septal defects. We identified protein altering, rare homozygous variants (RHVs) in the patient’s coding genome by whole exome sequencing. The patients had a median of seven damaging RHVs each, and our analysis revealed a total of 758 RHVs in 693 different genes. By prioritizing these genes based on variant severity, loss-of-function intolerance and specific expression in the developing heart, we identified a set of 23 candidate disease genes. These candidate genes were significantly enriched for genes known to cause heart defects in recessive mouse models (P < 2.4e−06). In addition, we found a significant enrichment of cilia genes in both the initial set of 693 genes (P < 5.4e−04) and the 23 candidate disease genes (P < 5.2e−04). Functional investigation of ADCY6 in cell- and zebrafish-models verified its role in heart development. Our results confirm a significant role for cilia genes in recessive forms of CHD and suggest important functions of cilia genes in cardiac septation.

Depositional architecture of early rift non-marine systems and implications for reservoir development: Oligocene to Miocene Al Wajh Formation, Midyan Basin of Red Sea, Saudi Arabia - Muhammad Naveed Butt; Arif Hussain; Muhammad Hammad Malik; Abduljamiu O. Amao; Ardiansyah Koeshidayatullah; Cornel Olariu; Abdulwahab Muhammad Bello; Khalid Al-Ramadan (Marine and Petroleum Geology, 2024)

Greenly synthesized zinc oxide nanoparticles: An efficient, cost-effective catalyst for dehydrogenation of formic acid and with improved antioxidant and phyto-toxic properties - Sami Ullah; Muhammad Shaban; Abu Bakar Siddique; Anam Zulfiqar; Naveed Shahzad Lali; Muhammad Naeem-ul-Hassan; Muhammad Imran Irfan; Muhammad Sher; Muhammad Fayyaz ur Rehman; Ali Hanbashi; Fahad Y. Sabei; Hatem M.A. Amin; et al. (Journal of Environmental Chemical Engineering, 2024)

Modulating glucose metabolism and relieving hypoxia for enhanced Chemo/Photoimmunotherapy with photosensitizing enzymatic nanodrugs - Zhiyuan Zheng; Shan Lu; Yue Wu; Ayşe Başak Kayitmazer; Ayyaz Ahmad; Naveed Ramzan; Muhammad Shahid Rafique; Jintao Yang; Xiaolong Zhou; Yisheng Xu; Yi Si (Chemical Engineering Journal, 2024)

Revolutionizing soybean genomics: How CRISPR and advanced sequencing are unlocking new potential - Muhammad Khuram Razzaq; Muhammad Naveed Babur; Muhammad Jawad Akbar Awan; Ghulam Raza; Mehwish Mobeen; Ali Aslam; Kadambot H. M. Siddique (Functional & Integrative Genomics, 2024)

Synthesis and characterization of Ca-alginate/CuO bionanocomposite for removal of Reactive Yellow 145 dye: a green approach towards sustainability - Saman Shams; Shumaila Kiran; Tahsin Gulzar; Muhammad Naveed Anjum (Clean Technologies and Environmental Policy, 2024)

Nanomedicine: Patuletin-conjugated with zinc oxide exhibit potent effects against Gram-negative and Gram-positive bacterial pathogens - Naveed Ahmed Khan; Adeelah Alvi; Saif Alqassim; Noor Akbar; Bushra Khatoon; Muhammad Kawish; Shaheen Faizi; Muhammad Raza Shah; Bader S. Alawfi; Ruqaiyyah Siddiqui (BioMetals, 2024)

Growth, body composition, lipid profile, and peroxidation, physiological stress, and blood metabolic indicators in Labeo rohita fed a fish oil replacement with blended linseed and sunflower oils - Muhammad Asghar; Noor Khan; Mahroze Fatima; Murat Arslan; Simon John Davies; Naveed ul Haque (Aquaculture International, 2024)

Evaluation of Heavy Metal Concentration in Different Organs of Labeo rohita in Water and Sediment of Marala Ravi Link Canal (MRL) and Upper Chenab Canal (UCC) of Chenab River, Pakistan, and Their Health Implications - Waqas Ahmad; Muhammad Samee Mubarik; Sajid Yaqub Qureshi; Naveed Ahmad Khan (Biological Trace Element Research, 2024)

Flavonoids from Pistacia chinensis subsp. integerrima with leishmanicidal activity: computational and experimental evidence - Abdur Rauf; Umer Rashid; Abdullah Muhammad Shbeer; Mohammed Al-Ghorbani; Naveed Muhammad; Anees Ahmed Khalil; Humaira Naz; Rohit Sharma; Giovanni Ribaudo (Natural Product Research, 2024)

CRISPR/Cas-mediated genome editing for efficient tomato breeding: past achievements and future directions - Muhammad Naeem; Wajid Zaman; Saddam Saqib; Asim Shahzad; Saeed ur Rahman; Naveed Ahmad (South African Journal of Botany, 2024)

Mineral Metamorphosis: Tracing the static and dynamic nexus between minerals and global south markets - Shoaib Ali; Muhammad Naveed; Nassar S. Al-Nassar; Nawazish Mirza (Resources Policy, 2024)

Metabolites-induced co-evolutionary warfare between plants, viruses, and their associated vectors: So close yet so far away - Naveed Ahmad; Hamad Hussain; Muhammad Naeem; Saeed ur Rahman; Khalid Ali Khan; Babar Iqbal; Abdul Wakeel Umar (Plant Science, 2024)

Effect of alfalfa-grass mixed culture and inoculation with Azotobacter and Rhizobium on soil biological properties and nutrient transformation activities - Jiri Holatko; Martin Brtnicky; Antonin Kintl; Tivadar Baltazar; Ondrej Malicek; Adnan Mustafa; Jiri Skladanka; Jiri Kucerik; Saud Alamri; Jan Lochman; Pavel Horky; Daniela Knotova; et al. (European Journal of Soil Biology, 2024)

Phytochemical profile, nutritional and medicinal value of Nigella sativa - Shabbir Hussain; Aqsa Rukhsar; Munawar Iqbal; Qurat ul Ain; Jahanzaib Fiaz; Noman Akhtar; Maria Afzal; Naveed Ahmad; Iqbal Ahmad; Wissem Mnif; Muhammad Hashir Khalid (Biocatalysis and Agricultural Biotechnology, 2024)

Diagenetic variability in Tertiary, syn-rift mixed siliciclastic‑carbonate depositional system (Lower Musayr Formation), Red Sea, Saudi Arabia - Arif Hussain; Abdulwahab Bello; Muhammad Naveed Butt; Muhammad Hammad Malik; Ardiansyah Koeshidayatullah; Abduljamiu Amao; Cornel Olariu; Khalid Al-Ramadan (Sedimentary Geology, 2024)

An updated and gridded probabilistic seismic hazard assessment of Quetta city, Pakistan using multiple source models - Bilal Saif; Mohammad Tahir; Muhammad Ali Shah; Muhammad Naveed Mushtaq; Muhammad Yousaf Khan; Azmat Azad; Talat Iqbal (Journal of Asian Earth Sciences, 2024)

Improving the efficiency of photovoltaic-thermoelectric generator system using novel flying squirrel search optimization algorithm: Hybrid renewable and thermal energy system (RTES) for electricity generation - Muhammad Yaqoob Javed; Aamer Bilal Asghar; Khazina Naveed; Ali Nasir; Basem Alamri; Muhammad Aslam; Essam A. Al-Ammar; Zsolt Conka (Process Safety and Environmental Protection, 2024)

Characterizations of biogenic selenium nanoparticles and their anti-biofilm potential against Streptococcus mutans ATCC 25175 - Binbin Si; Yang Yang; Muhammad Naveed; Fenghuan Wang; Malik Wajid Hussain Chan (Journal of Trace Elements in Medicine and Biology, 2024)

An innovative perovskite oxide enabling improved efficiency for low-temperature ceramic electrochemical cells - Yuzheng Lu; M. A. K. Yousaf Shah; Naveed Mushtaq; Muhammad Yousaf; Nabeela Akbar; Naila Arshad; Sultan Irshad (Fuel, 2024)

Silicon and Biochar Synergistically Stimulate Nutrients Uptake, Photosynthetic Pigments, Gaseous Exchange and Oxidative Defense to Improve Maize Growth Under Salinity - Sajid Mahmood; Samir G. Al-Solaimani; Samrah Shams; Sahar Naveed; Basit Haider; Muhammad Naveed; Rehmat Ali; Muhammad Waqas (Water, Air, & Soil Pollution, 2024)

Endophytic Bacillus spp. Mediated Plant Growth Promotion of Tomato Seedlings and Suppression of Meloidogyne incognita and Fusarium oxysporum Disease Complex - Ambreen Maqsood; Muhammad Naveed Aslam; Huma Khaliq; Muhammad Taimoor Shakeel; Haiyan Wu; Shah Fahad (Journal of Plant Growth Regulation, 2024)

Biodegradation of PVCs through in-vitro identification of Bacillus albus and computational pathway analysis of ABH enzyme - Muhammad Naveed; Rida Naveed; Tariq Aziz; Arooj Azeem; Mahrukh Afzal; Muhammad Waseem; Metab Alharbi; Abdulrahman Alshammari; Abdullah F. Alasmari; Thamer H. Albekairi (Biodegradation, 2024)

Progress, challenges, and prospects of MOF-based adsorbents for phosphate recovery from wastewater - Muhammad Naveed Afridi; Sawaira Adil; Battuya Byambaa; Muhammad Sohail; Aziz-Ur-Rahim Bacha; Jingwen Wang; Chaolin Li (Journal of Water Process Engineering, 2024)

Sunlight-assisted green synthesis of gold nanocubes using horsetail leaf extract: A highly selective colorimetric sensor for Pb2+, photocatalytic and antimicrobial agent - Abdul Waheed Khan; Naveed Shahzad Lali; Fahad Y. Sabei; Muhammad Imran Irfan; Muhammad Naeem-ul-Hassan; Muhammad Sher; Awaji Y. Safhi; Abdullah Alsalhi; Ahmed H. Albariqi; Faroq Kamli; Hatem M.A. Amin; Azhar Abbas (Journal of Environmental Chemical Engineering, 2024)

Seeding detection and distribution evaluation using the developed automatic maize seeding machine - Yunxia Li; Zhao Zhang; Afshin Azizi; Muhammad Hilal Kabir; C. Igathinathane; Xiqing Wang; Muhammad Naveed Tahir; Xiongzhe Han; Man Zhang (Computers and Electronics in Agriculture, 2024)

Bioactive compounds isolated from Solanum nigrum remarkably inhibit cancerous activity in cancer cell lines - Aisha Nawaz; Adil Jamal; Amina Arif; Shumaila Kiran; Muhammad Naveed Shahid; Shafia Arshad; Zeeshan Shamim (South African Journal of Botany, 2024)

Depositional cyclicity of lower Cambrian strata in the NW Himalayas: Regional sequence stratigraphy of the Indian passive margin - Tariq Mahmood; Naveed Ahsan; Muhammad Armaghan Faisal Miraj (Marine and Petroleum Geology, 2024)

Modulating plant-soil microcosm with green synthesized ZnONPs in arsenic contaminated soil - Asad Rehman; Saeed ur Rahman; Pengli Li; Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Muhammad Azam; Junfeng Cao; Muhammad Sanaullah Malik; Mouna Jeridi; Naveed Ahmad; Khulood Fahad Alabbosh; Qunlu Liu; et al. (Journal of Hazardous Materials, 2024)

Influences of emerging drying technologies on rice quality - Naveed Mahmood; Yanhong Liu; Xu Zheng; Zeeshan Munir; R. Pandiselvam; Yue Zhang; Mansab Ali Saleemi; Harimana Yves; Muhammad Sufyan; Dengwen Lei (Food Research International, 2024)

Assessment of heavy metals level in chicken with indeterminate analysis in localities of Lahore, Pakistan - Naveed Ahmad; Usama Afzal; Ramna Zafar; Muhammad Arslan; Saira Riaz; Shahzad Naseem; Muhammad Naeem; Adeena Fatima; Mubashar Ali; Muhammad Aslam (Environmental Monitoring and Assessment, 2024)

Soil microplastics: Impacts on greenhouse gasses emissions, carbon cycling, microbial diversity, and soil characteristics - Ismail Khan; Muhammad Tariq; Khulood Fahad Alabbosh; Abdul Rehman; Abdul Jalal; Asif Ali Khan; Muhammad Farooq; Guanlin Li; Babar Iqbal; Naveed Ahmad; Khalid Ali Khan; Daolin Du (Applied Soil Ecology, 2024)

Fluorescence Spectroscopy Based Characterization of Flaxseed Oil - Muhammad Saleem; Naveed Ahmad (Journal of Fluorescence, 2024)

Fostering sustainability and green innovation reporting in manufacturing firms: an investigation of barriers through ISM-MICMAC approach - Rehana Naheed; Muhammad Waqas; Naveed Ahmad; Muzaffar Iqbal; Muhammad Ismail (Environment, Development and Sustainability, 2024)

Divergent responses of phosphorus solubilizing bacteria with P-laden biochar for enhancing nutrient recovery, growth, and yield of canola (Brassica napus L.) - Muhammad Farhan Qadir; Muhammad Naveed; Khuram Shehzad Khan; Tooba Mumtaz; Taqi Raza; Waqas Mohy-Ud-Din; Adnan Mustafa (Chemosphere, 2024)

Electricity shortfalls and financial leverage of listed firms in Pakistan - Muhammad Akhtar; Muhammad Haris; Hafiz Muhammad Naveed; Yasir Rasool; Mamdouh Abdulaziz Saleh Al-Faryan (Utilities Policy, 2024)

Prediction of drought regulating gene (s) in barley (Hordeum vulgare L.) using express sequence tags (ESTs) through in silico approaches - Muhammad Naveed Shahid; Fatima Maqbool; Saifullah (South African Journal of Botany, 2024)

Self-assembled micelles loaded with itraconazole as anti-Acanthamoeba nano-formulation - Komal Rao; Muhammad Abdullah; Usman Ahmed; Hashi Isse Wehelie; Muhammad Raza Shah; Ruqaiyyah Siddiqui; Naveed A. Khan; Bader S. Alawfi; Ayaz Anwar (Archives of Microbiology, 2024)

Synergistic effect of Paclobutrazol and silver nanoparticles (AgNPs) control the pod shattering in canola (Brassica napus L.) via physiological interferences: a mechanistic overview - Habib Ali; Imran Mahmood; Ghulam Qadir; Naveed Iqbal Raja; Fozia Abasi; Mukhtar Ahmed; Muhammad Faizan Ali; Husnain Jawad; Jarosław Proćków (Acta Physiologiae Plantarum, 2024)

Does green tax theory affect the environmental sustainability and protection? - Muhammad Naveed Ahmad; Xiaoguang Zhou; Sagheer Muhammad; Malik Shahzad Shabbir (Environment, Development and Sustainability, 2024)

Sustainable porous graphene/Co-MOF for the removal of water pollutants: Combined theoretical and experimental studies - Zahira Bano; Muhammad Akram; Naveed Zafar Ali; Muhammad Usman Khan; Fengyun Wang; Linrui Li; Mingzhu Xia (Journal of Water Process Engineering, 2024)

Expression of BSN314 lysozyme genes in Escherichia coli BL21: a study to demonstrate microbicidal and disintegarting potential of the cloned lysozyme - Muhammad Naveed; Sai Wen; Malik Wajid Hussain Chan; Fenghuan Wang; Sadar Aslam; Xian Yin; Baocai Xu; Asad Ullah (Brazilian Journal of Microbiology, 2024)

An Aedes–Anopheles Vaccine Candidate Supplemented with BCG Epitopes Against the Aedes and Anopheles Genera to Overcome Hypersensitivity to Mosquito Bites - Muhammad Naveed; Urooj Ali; Tariq Aziz; Rida Naveed; Sarmad Mahmood; Muhammad Mustajab Khan; Metab Alharbi; Thamer H. Albekairi; Abdullah F. Alasmari (Acta Parasitologica, 2024)

Heart rate as an indicator of stress during the critical swimming speed test of farmed Atlantic salmon ( Salmo salar L.) - Muhammad Naveed Yousaf; Øyvind Røn; Frederike Keitel‐Gröner; Charles McGurk; Alex Obach (Journal of Fish Biology, 2024)
A swim tunnel is to fish as a treadmill is to humans, and is a device used for indirect measuring of the metabolic rate. This study aims to explore the fish stress (if any) during the critical swimming test routines (fish handling, confinement, and swimming) using heart rate ( f H , heartbeat per minute) bio‐loggers in farmed Atlantic salmon ( Salmo salar L.). In addition, the recovery dynamics of exercised fish using f H were explored for 48 h post swim tests. Continuous f H data were acquired following the surgical implantation and throughout the trials, such as during fish handling, swim tests (critical swimming speed, U crit ), and 48 h post swim tests. After 3 weeks of surgical recovery, f H stabilized at 46.20 ± 1.26 beats min −1 , equalizing a ~38% reduction in f H recorded post‐surgical tachycardia (74.13 ± 1.44 beats min −1 ). Interestingly, f H was elevated by ~200% compared to baseline levels not only due to the U crit (92.04 ± 0.23 beats min −1 ) but also due to fish handling and confinement in the swim tunnel, which was 66% above the baseline levels (77.48 ± 0.34 beats min −1 ), suggesting fish stress. Moreover, significantly higher plasma cortisol levels (199.56 ± 77.17 ng mL −1 ) corresponding to a ~300% increase compared to baseline levels (47.92 ± 27.70 ng mL −1 ) were identified after U crit , predicting post‐swim test stress (physiological exhaustion). These findings reinforce the importance of fish acclimation in the swim tunnel prior to the swimming tests. However, f H dropped over the course of the 48‐h post‐swim test, but remained comparatively higher than the basal levels, suggesting fish should be given at least 48 h to recover from handling stress for better fish welfare. This study further explored the influence of fish tagging on U crit , which resulted in reduced swimming capabilities of tagged fish (1.95 ± 0.37 body lengths s −1 ) compared to untagged fish (2.54 ± 0.42 body length s −1 ), although this was not significant ( p = 0.06), and therefore future tagging studies are warranted.

Retraction Note: Poloxamer-407-Co-Poly (2-Acrylamido-2-Methylpropane Sulfonic Acid) Cross-linked Nanogels for Solubility Enhancement of Olanzapine: Synthesis, Characterization, and Toxicity Evaluation - Kifayat Ullah Khan; Naveed Akhtar; Muhammad Usman Minhas (AAPS PharmSciTech, 2024)

FinTech-powered integration: Navigating the static and dynamic connectedness between GCC equity markets and renewable energy cryptocurrencies - Shoaib Ali; Muhammad Naveed; Manel Youssef; Imran Yousaf (Resources Policy, 2024)

Influence of distributor plate design on mixing characteristics of rice husk biomass in a bubbling fluidized bed gasifier: An experimental and CFD study - Naveed Raza; Muhammad Ahsan (Fuel, 2024)

Histotoxicity induced by copper oxide nanoparticles (CuO-NPs) on developing mice (Mus musculus) - Munir Ahmad; Muhammad Khalil Ahmad Khan; Naveed Ahmad; Munazza Parveen; Khurram Shahzad; Ali Hasan (Food and Chemical Toxicology, 2024)

Theoretical and experimental explored tailored hybrid H+/O2– ions conduction: Bridged for high performance fuel cell and water electrolysis - Zuhra Tayyab; Sajid Rauf; Muhammad Bilal Hanif; Hafiz Imran Ahmad Qazi; Naveed Mushtaq; Martin Motola; Sining Yun; Chen Xia; Dmitry A. Medvedev; Muhammad Imran Asghar; Abdullah N. Alodhayb; Arshad Hussain; et al. (Chemical Engineering Journal, 2024)

Antibacterial effects of quercetagetin are significantly enhanced upon conjugation with chitosan engineered copper oxide nanoparticles - Adeelah Alvi; Saif Alqassim; Naveed Ahmed Khan; Bushra Khatoon; Noor Akbar; Muhammad Kawish; Shaheen Faizi; Muhammad Raza Shah; Ahmad M. Alharbi; Hasan Alfahemi; Ruqaiyyah Siddiqui (BioMetals, 2024)

Melatonin supplementation alleviates drought stress in peach (Prunus persica) seedlings by improving photosynthesis, root morphological traits, and antioxidant defense system - Shahid Iqbal; Faisal Hayat; Mujahid Hussain; Naveed Mushtaq; Muneer Rehman; Alaiha Asif; Ummara Khan; Muhammad Adnan Shahid (Acta Physiologiae Plantarum, 2024)

A comprehensive review: persistence, circulative transmission of begomovirus by whitefly vectors - Muhammad Aqib Idrees; Arzlan Abbas; Babu Saddam; Muhammad Hamid Bashir; Hassan Naveed; Ahmad Kamran Khan; Muhammad Zulqar Nain Dara (International Journal of Tropical Insect Science, 2024)

The fourth industrial revolution in the food industry—part II: Emerging food trends - Abdo Hassoun; Alaa El-Din Bekhit; Anet Režek Jambrak; Joe M. Regenstein; Farid Chemat; James D. Morton; María Gudjónsdóttir; María Carpena; Miguel A. Prieto; Paula Varela; Rai Naveed Arshad; Rana Muhammad Aadil; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Copolymerization of ethylene and isoprene via silicon bridge metallocene [rac-Me2Si(2-Me-4-Ph-Ind)2ZrCl2] catalyst: A new way to control the composition and microstructure of copolymers - Amjad Ali; Ahmad Naveed; Anna Maroń; Muhammad Adnan Younis; Jamile Mohammadi Moradian; Balal Yousaf; Tariq Aziz; Rai Nauman Ali; Naushad Ahmad; Suliman Yousef Alomar; Fan Zheqiang; Li Guo (Chemosphere, 2024)

Beyond contamination: Enhancing plant tolerance to arsenic through phytobial remediation - Saeed ur Rahman; Xinxin Liu; Muhammad Khalid; Asad Rehman; Junfeng Cao; Sadaf-Ilyas Kayani; Muhammad Naeem; Naveed Ahmad; Abid Ali Khan; Muhammad Aamir Manzoor; Chang Zhao; Haoxin Tan; et al. (South African Journal of Botany, 2024)

Recent development in advanced photocatalytic materials for oxidative removal of bisphenol - Hubdar Ali Maitlo; ZhongZheng Hu; Imran Ali; Ghulamullah Maitlo; Dae-Hwan Lim; Muhammad Naveed Afridi; Minghua Zhou (Journal of Cleaner Production, 2024)

Depositional and diagenetic controls on the reservoir quality of Early Miocene syn-rift deep-marine sandstones, NW Saudi Arabia - Muhammad Naveed Butt; Stephen G. Franks; Arif Hussain; Abduljamiu Olalekan Amao; Abdulwahab Muhammad Bello; Khalid Al-Ramadan (Journal of Asian Earth Sciences, 2024)

Investigating the impact of climate change on trend shifts of vegetation growth in Gilgit Baltistan - Zulqarnain Satti; Muhammad Naveed; Muhammad Shafeeque; Lanhai Li (Global and Planetary Change, 2024)

Phytotoxicity of radionuclides: A review of sources, impacts and remediation strategies - Shahzaib Ali; Sadia Babar Baloch; Jaroslav Bernas; Petr Konvalina; Eze Festus Onyebuchi; Muhammad Naveed; Hassan Ali; Zameer Hussain Jamali; Mohammad Tahsin Karimi Nezhad; Adnan Mustafa (Environmental Research, 2024)

Retraction Note: A new cationic palladium(II) dithiocarbamate exhibits anti-inflammatory, analgesic, and antipyretic activities through inhibition of inflammatory mediators in in vivo models - Muhammad Naveed; Shahan Zeb Khan; Sara Zeeshan; Adnan Khan; Bushra Shal; Ayesha Atiq; Hussain Ali; Rahim Ullah; Zia-ur-Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

How ESG reporting is effected by sustainable finance and green innovation: moderating role of sales growth - Fawad Rauf; Wang Wanqiu; Khwaja Naveed; Syed Usman Qadri; Muhammad Sibt e Ali (Environmental Science and Pollution Research, 2023)

Bacterial inoculation remediates heavy metals toxicity through modulating biochemicals and antioxidant enzymes of Daucus carota L. grown in lead contaminated soil - Naima Huma Naveed; Naveed Abbas Nasir; Anis Ali Shah; Tahir Shahzad; Nasim Ahmad Yasin; Zain Ali; Muhammad Jamil; Talha Javed; Aamir Ali (South African Journal of Botany, 2023)

Synergy between industry and agriculture: Techno-economic and life cycle assessments of waste recovery for crop growth in glasshouses - Lewis J. McDonald; Ariane S.S. Pinto; Muhammad Naveed Arshad; Rebecca L. Rowe; Iain Donnison; Marcelle McManus (Journal of Cleaner Production, 2023)

Abiogenic silicon: Interaction with potentially toxic elements and its ecological significance in soil and plant systems - Babar Hussain; Luqman Riaz; Kun Li; Kashif Hayat; Naveed Akbar; Muhammad Zakwan Hadeed; Bowei Zhu; Shengyan Pu (Environmental Pollution, 2023)

Variation in Soil C and P Fractions Associated with Microbial Biomass - Khuram Shehzad Khan; Muhammad Naveed; Muhammad Farhan Qadir; Adeel Ahmad; Hafiz Hassan Javed; Allah Ditta (Journal of Soil Science and Plant Nutrition, 2023)

Synthesis and Characterization of Cosmetic Grade Ionic Liquids and Their Application as Skin Whitening Agents - Farah Bashir; Nawshad Muhammad; Meshal Alshamrani; Maliha Uroos; Ahmad Salawi; Awaji Y. Safhi; Naveed Ahmed; Abdullah Alsalhi; Fahad Y. Sabei; Osama A. Madkhali (Journal of Pharmaceutical Innovation, 2023)

Curative potential of Populus ciliata Wall ex. Royle extract against adjuvant-induced arthritis and peripheral neuropathy in Wistar rats - Amna Tahir; Muhammad Furqan Akhtar; Ammara Saleem; Muhammad Naveed; Basiru Olaitan Ajiboye; Fareeha Anwar; Aslam Khan (Inflammopharmacology, 2023)

RETRACTED ARTICLE: Demystifying the association between economic development, transportation, tourism, renewable energy, and ecological footprint in Bay of Bengal Initiative for Multi-Sectoral Technical and Economic Cooperation region during globalization mode - Muhammad Naveed; Minhazul Islam; Muhammad Usman; Mustafa Kamal; Mohammad Faisal Khan (Environmental Science and Pollution Research, 2023)

Melatonin-induced development of adventitious roots, biosynthesis of secondary cell products and greener synthesis of silver nanoparticles for biological activities using Indigofera heterantha - Irfan Ullah; Muhammad Sajid; Nisar Ahmad; Naveed Ahmad; Kamran Rauf; Rabia Khalil; Babar Iqbal; Mazhar Ali; Marcelo Carvalho Minhoto Teixeira Filho; Mohammad K. Okla; Hamada AbdElgawad; Asghar Khan; et al. (South African Journal of Botany, 2023)

DNA base analysis: An effective tool to resolve taxonomic uncertainty and establish phylogenetic relationship in cryptic genotypes of Pyrus (pear), Rosaceae - Muhammad Saeed Akhtar; Shahid Ullah Khan; Ebraheem Abdu Musad Saleh; Said Muhammad; Mohammad Islam; Umber Zaman; Khalil ur Rehman; Gul Nawab; Muhammad Naveed Akhtar; Nabil A. Alhakamy; M.K. Rasha Ibrahim; Ehab A. Abdelrahman (South African Journal of Botany, 2023)

Permo-Triassic cyclicity on the western shoulder of Muzaffarabad-Hazara paleo-high, during the oceanisation of Neo-Tethys - Tariq Mahmood; Naveed Ahsan; Muhammad Armaghan Faisal Miraj; Shaukat Ali; Saif ur Rahman; Muhammad Jawad Munawar (Marine and Petroleum Geology, 2023)

Design and numerical analysis of inverted well technique for aquifer recharge estimation - Muhammad Jahanzaib; Muhammad Kaleem Ullah; Muhammad Naveed Afridi; Muhammad Qasim (Groundwater for Sustainable Development, 2023)

Exploring perovskite oxide for advancing salt-resistant photothermal membranes and reliable thermoelectric generators - Naila Arshad; Muhammad Sultan Irshad; Muneerah Alomar; Jinming Guo; M. Sohail Asghar; Naveed Mushtaq; M.A.K. Yousaf; Uzma Ghazanfar; Matiullah Shah; Xianbao Wang; Yabin Hao; Lien Thi Do; et al. (Chemical Engineering Journal, 2023)

Co-occurrence of mycotoxins and other fungal metabolites in total mixed rations of cows from dairy farms in Punjab, Pakistan - Felipe Penagos-Tabares; Mubarik Mahmood; Muhammad Zafar Ullah Khan; Hafiz Muhammad Amjad Talha; Muhammad Sajid; Kanwal Rafique; Saima Naveed; Johannes Faas; Juan Ignacio Artavia; Michael Sulyok; Anneliese Müller; Rudolf Krska; et al. (Mycotoxin Research, 2023)
After India and the USA, Pakistan is the third country leading in global dairy production, a sector of very high socioeconomic relevance in Asia. Mycotoxins can affect animal health, reproduction and productivity. This study analysed a broad range of co-occurring mycotoxins and fungal secondary metabolites derived from Alternaria , Aspergillus , Fusarium , Penicillium and other fungal species. To complete this, a validated multi-metabolite liquid chromatography/electrospray ionization-tandem mass spectrometric (LC/ESI–MS/MS) method was employed, detecting 96 of > 500 tested secondary fungal metabolites. This first preliminary study demonstrated that total mixed rations (TMRs) ( n = 30) from big commercial dairy cattle farms (> 200 lactating cows) in Punjab, Pakistan, presented ubiquitous contamination with mixtures of mycotoxins. The mean of mycotoxins per sample was 14, ranging from 11 to 20 mycotoxins among all TMR samples. Metabolites derived from other fungi and Fusarium spp. showed the highest levels, frequency and diversity among the detected fungal compounds. Among the most prevalent mycotoxins were Fusarium toxins like fumonisins B1 (FB1) (93%), B2 (FB2) (100%) and B3 (FB3) (77%) and others. Aflatoxin B1 (AFB1) was evidenced in 40% of the samples, and 7% exceeded the EU maximum limit for feeding dairy cattle (5 µg/kg at 88% dry matter). No other mycotoxin exceeds the EU guidance values (GVs). Additionally, we found that dietary ingredients like corn grain, soybean meal and canola meal were related to increased contamination of some mycotoxins (like FB1, FB2 and FB3) in TMR from the province of Punjab, Pakistan. Among typical forage sources, the content of maize silage was ubiquitous. Individually, the detected mycotoxins represented relatively low levels. However, under a realistic scenario, long-term exposure to multiple mycotoxins and other fungal secondary metabolites can exert unpredictable effects on animal health, reproduction and productivity. Except for ergot alkaloids (73%), all the groups of metabolites (i.e. derived from Alternaria spp., Aspergillus spp., Fusarium spp., Penicillium spp. and other fungi) occurred in 100% of the TMR samples. At individual levels, no other mycotoxins than AFB1 represented a considerable risk; however, the high levels of co-occurrence with several mycotoxins/metabolites suggest that long-term exposure should be considered because of their potential toxicological interactions (additive or synergistic effects).

Environmental friendly utilization of plant wastes in combination as a source of natural colorants for binary mordanted silk dyeing - Nimra Amin; Shahid Adeel; Fazal-ur-Rehman; Muhammad Naveed Anjum (Environmental Science and Pollution Research, 2023)

First report of Geotrichum candidum causing rose blight disease in Pakistan - Muhammad Talha Ikram; Muhammad Naveed Aslam; Anam Moosa; Faisal Zulfiqar; Muhammad Taimoor Shakeel; Roshaan Ahmed; Muneeb Anwer; Atta ur Rehman Khan (Journal of Plant Pathology, 2023)

Experimental assessment of retrofitted damaged mortarless dry stacked interlocking masonry walls - Saeed Akbar; Akhtar Gul; Inayat Ullah Khan; Muhammad Haseeb; Khan Shahzada; Sajjad Wali Khan; Naveed Ahmad (Soil Dynamics and Earthquake Engineering, 2023)

Tailoring triple charge (O2−/H+/e−) conducting nature of Fe-based lanthanum doped samarium oxides for ceramic fuel cells (CFCs) - Muhammad Yousaf; Yuzheng Lu; Majid Niaz Akhtar; Ali Sarosh Khawaja; Khalid Mujasam Batoo; Sajjad Hussain; Asma Noor; Muhammad Akbar; Hu Enyi; M.A.K Yousaf Shah; Naveed Mushtaq; Bin Zhu (Fuel, 2023)

Sustainability of bioenergy – Mapping the risks & benefits to inform future bioenergy systems - Andrew James Welfle; Alberto Almena; Muhammad Naveed Arshad; Scott William Banks; Isabela Butnar; Katie Jane Chong; SamuelJ.G. Cooper; Helen Daly; Samira Garcia Freites; Fatih Güleç; Christopher Hardacre; Robert Holland; et al. (Biomass and Bioenergy, 2023)

Unveiling the potential of acidified cow dung in combination with plant growth promoting endophytes on growth, physiology, and yield improvement of maize in salt-affected soil - Muhammad Naveed; Rabail Zulekha; Khuram Shehzad Khan; Noman Younas; Muhammad Farhan Qadeer; Martin Brtnicky; Jiri Holatko; Adnan Mustafa (Arabian Journal of Geosciences, 2023)

Sustainable development through corporate social responsibility adoption and its drivers: evidence from corporate industrial sector - Hussain Bux; Zhe Zhang; Muhammad Tayyab Sohail; Naveed Ahmad; Adnan Ali (Environmental Science and Pollution Research, 2023)

Influence of soil microplastic contamination and cadmium toxicity on the growth, physiology, and root growth traits of Triticum aestivum L. - Babar Iqbal; Qaiser Javed; Ismail Khan; Muhammad Tariq; Naveed Ahmad; Hosam O. Elansary; Arshad Jalal; Guanlin Li; Daolin Du (South African Journal of Botany, 2023)

Identification, characterization and expression profiling of salt-stress responsive proteinase inhibitor in Gossypium arboreum L. - Muhammad Naveed Shahid; Sarfraz Kiani; Bushra Rashid; Tayyab Husnain (South African Journal of Botany, 2023)

Effect of NDF levels of complete pelleted diet and dietary transition period on rumen pH, growth performance, digestibility, and blood indices in fattening male goats - Muhammad Awais Khurshid; Muhammad Afzal Rashid; Muhammad Shahbaz Yousaf; Saima Naveed; Muhammad Qamer Shahid; Habib Ur Rehman (Small Ruminant Research, 2023)

Assessment of essential and toxic elemental concentrations in tumor and non-tumor tissues with risk of colorectal carcinoma in Pakistan - Muhammad Abdul Qayyum; Tahir Farooq; Aqsa Baig; Tanveer Hussain Bokhari; Muhammad Naveed Anjum; Mian Habib-ur-Rahman Mahmood; Ahmad Raza Ashraf; Khawaja Muddassir; Muhammad Ahmad (Journal of Trace Elements in Medicine and Biology, 2023)

Thermal analysis of integrated hydrate-based desalination system with intermediate fluid type LNG vaporizer - Elias M. Salilih; Muhammad Naveed Khan; Omar Bamaga; Iqbal Ahmed; Mohammad Albeirutty; Eydhah Almatrafi; Hani Abulkhair; Hisham Alhumade; Ahmed Bamasag; Mohammed G.H. Haidar (Journal of Cleaner Production, 2023)

Thermal Effects on the Quality Parameters of Extra Virgin Olive Oil Using Fluorescence Spectroscopy - Areeba Ansar; Naveed Ahmad; Mha Albqmi; Muhammad Saleem; Hina Ali (Journal of Fluorescence, 2023)

Quality Analysis of Canola and Mustard Oil Using Fluorescence Spectroscopy - Muhammad Saleem; Hina Ali; M. Bilal; Babar M. Atta; Naveed Ahmad (Journal of Fluorescence, 2023)

Beyond green and red: unlocking the genetic orchestration of tomato fruit color and pigmentation - Muhammad Naeem; Weihua Zhao; Naveed Ahmad; Lingxia Zhao (Functional & Integrative Genomics, 2023)

Quantifying irrigation water demand and supply gap using remote sensing and GIS in Multan, Pakistan - Muhammad Haseeb; Hafiz Umar Farid; Zahid Mahmood Khan; Muhammad Naveed Anjum; Akhlaq Ahmad; Muhammad Mubeen (Environmental Monitoring and Assessment, 2023)

Groundwater quality risk assessment using hydro-chemical and geospatial analysis - Hafiz Umar Farid; Hafiz Usman Ayub; Zahid Mahmood Khan; Ijaz Ahmad; Muhammad Naveed Anjum; Rana Muhammad Asif Kanwar; Muhammad Mubeen; Pervaiz Sakinder (Environment, Development and Sustainability, 2023)

Assessment of lead, cadmium, and mercury levels in the breast milk in Pakistani women - Naveed Ahmad; Abbas Muhammad; Ramna Zafar; Usama Afzal; Muhammad Aslam (Environmental Science and Pollution Research, 2023)

Nickel (Ni) phytotoxicity and detoxification mechanisms: A review - Adnan Mustafa; Usman Zulfiqar; Muhammad Zahid Mumtaz; Maja Radziemska; Fasih Ullah Haider; Jiri Holatko; Tereza Hammershmiedt; Muhammad Naveed; Hassan Ali; Antonin Kintl; Qudsia Saeed; Jiri Kucerik; et al. (Chemosphere, 2023)

Supplementation of Moringa based zinc oxide nanoparticles mitigates salt stress in Celosia argentea through reduced chloride (Cl −) uptake and modulation in physiochemical attributes - Musarrat Ramzan; Nabeera Naveed; Muhammad Zaheer Ahmed; Hina Ashraf; Anis Ali Shah; Muhammad Jamil; Zahoor Ahmad; Ryan Casini; Hosam O. Elansary (South African Journal of Botany, 2023)

Replacing ground Rhodes grass hay with soyhulls in the pelleted diet: effects on ingestive behavior, nutrient digestibility, blood metabolites, growth performance, and economic viability of intensive fattening Lohi lambs - Muhammad Khan; Muhammad Afzal Rashid; Muhammad Shahbaz Yousaf; Saima Naveed; Imran Mohsin; Habib Ur Rehman (Tropical Animal Health and Production, 2023)

Silicon Supplement Improves Growth and Yield Under Salt Stress by Modulating Ionic Homeostasis and Some Physiological Indices in Hordeum vulgare L - Muhammad Salim Akhter; Sibgha Noreen; Seema Mahmood; Muhammad Aqeel; Zafar Ullah Zafar; Muhammad Rashid; Muhammad Naveed Arshad; Muhammad Owais; Javid Ahmad; Kausar Hussain Shah (Journal of Soil Science and Plant Nutrition, 2023)

Unraveling the functional characterization of a jasmonate-induced flavonoid biosynthetic CYP45082G24 gene in Carthamus tinctorius - Yufei Wang; Zhiling Li; Naveed Ahmad; Xiaoxiao Sheng; Babar Iqbal; Muhammad Naeem; Nan Wang; Fengwei Li; Na Yao; Xiuming Liu (Functional & Integrative Genomics, 2023)

An overview of genome engineering in plants, including its scope, technologies, progress and grand challenges - Muhammad Sufyan; Umar Daraz; Sajjad Hyder; Usman Zulfiqar; Rashid Iqbal; Sayed M. Eldin; Farzana Rafiq; Naveed Mahmood; Khurram Shahzad; Muhammad Uzair; Sajid Fiaz; Iftikhar Ali (Functional & Integrative Genomics, 2023)

In-field deployable and facile nanosensor for the detection of pesticides residues - Naveed Akhtar Shad; Anam Munawar; Yasir Javed; Allah Rakha; Ahsan Riaz; Salah Ud Din; Iqra Zareef; Muhammad Munir Sajid; Muahmmad Farhan Khan; Sareen Akhtar; Midhat Salman (Analytica Chimica Acta, 2023)

Detection of BK and JC polyomaviruses in sewage water of the urban areas of Lahore, Pakistan - Rabia Ijaz; Naveed Shahzad; Muhammad Farhan Ul Haque (Biologia, 2023)

First record of Fusarium solani causing post-harvest Fusarium rot of Citrus reticulata Blanco cv. ‘Kinnow’ in Pakistan - Anam Moosa; Faisal Zulfiqar; Muhammad Naveed Aslam (Journal of Plant Pathology, 2023)

First report of leaf spot of Aloe vera caused by Curvularia spicifera in Pakistan - Roshaan Ahmed; Muhammad Naveed Aslam; Anam Moosa; Muhammad Taimoor Shakeel; Ambreen Maqsood (Journal of Plant Pathology, 2023)

Toxic effects of cadmium on the physiological and biochemical attributes of plants, and phytoremediation strategies: A review - Yanliang Li; Shafeeq Ur Rahman; Zhixin Qiu; Sher Muhammad Shahzad; Muhammad Farrakh Nawaz; Jianzhi Huang; Sadiq Naveed; Lei Li; Xiaojie Wang; Hefa Cheng (Environmental Pollution, 2023)

Anti-Balamuthia mandrillaris and anti-Naegleria fowleri effects of drugs conjugated with various nanostructures - Ruqaiyyah Siddiqui; Anania Boghossian; Saif S. Alqassim; Muhammad Kawish; Jasra Gul; Tooba Jabri; Muhammad Raza Shah; Naveed Ahmed Khan (Archives of Microbiology, 2023)

Challenges associated with cellulose composite material: Facet engineering and prospective - Tariq Aziz; Fazal Haq; Arshad Farid; Mehwish Kiran; Shah Faisal; Asmat Ullah; Naveed Ullah; Awais Bokhari; Muhammad Mubashir; Lai Fatt Chuah; Pau Loke Show (Environmental Research, 2023)

Role of silica-based porous cellulose nanocrystals in improving water absorption and mechanical properties - Tariq Aziz; Arshad Farid; Fazal Haq; Mehwish Kiran; Naveed Ullah; Shah Faisal; Amjad Ali; Farman Ullah Khan; Siming You; Awais Bokhari; Muhammad Mubashir; Lai Fatt Chuah; et al. (Environmental Research, 2023)

Spatial Pattern of Cotton Yield Variability and Its Response to Climate Change in Cotton Belt of Pakistan - Naveed Muhammad; Hongshi He; Shengwei Zong; Haibo Du; Zulqarnain Satti; Xinyuan Tan; Muhammad Yasir Qazi (Chinese Geographical Science, 2023)

Impact of depositional and diagenetic controls on reservoir quality of syn-rift sedimentary systems: An example from Oligocene-Miocene Al Wajh Formation, northwest Saudi Arabia - Abdulwahab Muhammad Bello; Muhammad Naveed Butt; Arif Hussain; Abduljamiu O. Amao; Cornel Olariu; Ardiansyah I. Koeshidayatullah; Muhammad H. Malik; Murtada Al-Hashem; Khalid Al-Ramadan (Sedimentary Geology, 2023)

Pulsed electric field as a promising technology for solid foods processing: A review - Cheng Zhang; Xiaomei Lyu; Rai Naveed Arshad; Rana Muhammad Aadil; Yanjun Tong; Wei Zhao; Ruijin Yang (Food Chemistry, 2023)

Plant microbe mediated enhancement in growth and yield of canola (Brassica napus L.) plant through auxin production and increased nutrient acquisition - Misha Iqbal; Muhammad Naveed; Muhammad Sanaullah; Martin Brtnicky; M. Iftikhar Hussain; Jiri Kucerik; Jiri Holatko; Adnan Mustafa (Journal of Soils and Sediments, 2023)

Preliminary Geoheritage Assessment of The Gharam Chashma Granitic Batholith (GCGB), Southern Margin of Asian Plate, NW Pakistan: Multiple Constraints from Field Evidence, Petrology, and Physicomechanical Properties - Abbas Ali Naseem; Muhammad Naveed Anjum; Muhammad Yaseen; Muhammad Ali; Waqar Inam; Syed Haroon Ali; Jawad Ahmad; Anees Ahmad Bangash (Geoheritage, 2023)

Cotton cultivated area detection and yield monitoring combining remote sensing with field data in lower Indus River basin, Pakistan - Muhammad Naveed; Hong S. He; Shengwei Zong; Haibo Du; Zulqarnain Satti; Hang Sun; Shuai Chang (Environmental Monitoring and Assessment, 2023)

Alumina supported copper oxide nanoparticles (CuO/Al2O3) as high-performance electrocatalysts for hydrazine oxidation reaction - Safia Khan; Syed Sakhawat Shah; Naveed Kausar Janjua; Ayse Bayrakçeken Yurtcan; Muhammad Tariq Nazir; Khadijah Mohammedsaleh Katubi; Norah Salem Alsaiari (Chemosphere, 2023)

Effect of straw particle size in high grain complete pelleted diet on growth performance, rumen pH, feeding behavior, nutrient digestibility, blood and carcass indices of fattening male goats - Muhammad Awais Khurshid; Muhammad Afzal Rashid; Muhammad Shahbaz Yousaf; Saima Naveed; Muhammad Qamer Shahid; Habib Ur Rehman (Small Ruminant Research, 2023)

Treatment of Anaerobically Digested Distillery Spent Wash Using Electrocoagulation with Al-SS-Al Electrode Configuration - Waheed Ali Khokhar; Muhammad Rizwan; Naveed Ahmed Qambrani (Water, Air, & Soil Pollution, 2023)

Physically separated soil organic matter pools as indicators of carbon and nitrogen change under long-term fertilization in a Chinese Mollisol - Adnan Mustafa; Qudsia Saeed; Mohammad Tahsin Karimi Nezhad; Sun Nan; Gao Hongjun; Zhu Ping; Muhammad Naveed; Xu Minggang; Avelino Nú nez-Delgado (Environmental Research, 2023)

Evaluation of single-phase net metering to meet renewable energy targets: A case study from Pakistan - Muhammad Usman Tahir; Kiran Siraj; Syed Faizan Ali Shah; Naveed Arshad (Energy Policy, 2023)

Analysis of Temperature Data Using the Innovative Trend Pivot Analysis Method and Trend Polygon Star Concept: A Case Study of Soan River Basin, Potohar, Pakistan - Fiaz Hussain; Ray-Shyan Wu; Ghulam Nabi; Rana Shahzad Noor; Muhammad Naveed Anjum; Muhammad Azam; Arslan Afzal (Pure and Applied Geophysics, 2023)
The trend analysis approach is used to estimate changing climate and its impact on the environment, agriculture and water resources. Innovative polygonal trend analyses are qualitative methods applied to detect changes in the environment. In this study, the Innovative Trend Pivot Analysis Method (ITPAM) and Trend Polygon Star Concept Method were applied for temperature trend detection in Soan River Basin (SRB), Potohar region, Pakistan. The average monthly temperature data (1995–2020) for 11 stations were used to create polygon graphics. Trend length and slope were calculated separately for arithmetic mean and standard deviation. The innovative methods produced useful scientific information, with the identification of monthly shifts and trend behaviors of temperature data at different stations. Some stations showed an increasing trend and others showed decreasing behavior. This increasing and decreasing variability is the result of climate change. The winter season temperature is increasing, and the months of December to February are getting warmer. Summer is expanding and pushing autumn towards winter, swallowing the early period of the cold season. The monthly polygonal trends with risk graphs depicted a clear picture of climate change in the Potohar region of Pakistan. The phenomena of observed average temperature changes, indicated by both qualitative methods, are interesting and have the potential to aid water managers’ understanding of the cropping system of the Potohar region.

Biomass energy consumption and sustainable development: empirical evidence from Asian economies - Naveed Asghar; Muhammad Tariq Majeed; Muhammad Waqas Khan; Awais Anwar (Environmental Science and Pollution Research, 2023)

Success of Aquaculture Industry with New Insights of Using Insects as Feed: A Review - Amna Hameed; Waqar Majeed; Muhammad Naveed; Uzma Ramzan; Matteo Bordiga; Maryam Hameed; Saud Ur Rehman; Naureen Rana (Fishes, 2022)
Most of world’s fish and seafood are produced by aquaculture, which is one of the biggest contributors to the world’s food security. The substantial increase in prices of conventional feed ingredients and the over-exploitation of natural resources are some of the biggest constraints to aquaculture production. To overcome this stress, different approaches and techniques are used, among which the use of non-conventional feed ingredients in the aquaculture sector is the most recent approach. Different non-conventional feed ingredients such as plant-based products, algae (both micro and macroalgae), single-cell protein (bacteria and yeast), and insect meal are currently used in aquaculture for sustainable food production. Amongst all these novel ingredients, insects have greater potential to replace fishmeal. The existence of about 1.3 billion tons of food and agriculture waste from the food chain supply poses a serious environmental threat. Insects are tiny creatures that can thrive on organic waste and thus can convert the waste to wealth by the bioconversion and nutritional upcycling of organic waste. Insects have the potential to recover nutrients from waste aquaculture products, and many fish species feed on insects naturally. Therefore, employing insects in the aquaculture sector to replace fishmeal is an eco-friendly approach. The present review briefly highlights emerging non-conventional feed ingredients, with special attention given to insects. The current review also focuses on the nutritional value of insects, factors affecting the nutritional value of insects, potential insects that can be employed in the aquaculture sector, the physiological response of fish when fed with insect meal, techno-functional properties of insect meal, and emerging approaches for addressing possible downsides of employing insect meal in fish diets. Finally, it suggests avenues for further research into these inventive fishmeal replacements.

Efficacy of Different Endophytic Bacterial Strains in Enhancing Growth, Yield, and Physiological and Biochemical Attributes of Linum usitatissimum L - Khuram Shehzad Khan; Muhammad Farhan Qadir; Adeel Ahmad; Muhammad Naveed; Taqi Raza; Allah Ditta (Journal of Soil Science and Plant Nutrition, 2022)

Correction to: Interactive Effect of Boron Application Methods and Boron-Tolerant Bacteria (Bacillus sp. MN54) Improves Nodulation, Grain Yield, Profitability and Biofortification of kabuli Chickpea Grown Under Irrigated and Rainfed Conditions - Noman Mehboob; Tauqeer Ahmad Yasir; Sami Ul-Allah; Ahmad Nawaz; Muhammad Naveed; Mubshar Hussain (Journal of Soil Science and Plant Nutrition, 2022)

Transition metal-doped SnO2 and graphene oxide (GO) supported nanocomposites as efficient photocatalysts and antibacterial agents - Tauseef Munawar; Muhammad Shahid Nadeem; Faisal Mukhtar; Muhammad Naveed ur Rehman; Muhammad Riaz; Sana Batool; Murtaza Hasan; Faisal Iqbal (Environmental Science and Pollution Research, 2022)

Amelioration of lead toxicity by ascorbic acid in sugarcane (Saccharum officinarum L.) under in vitro condition - Yasmeen Saleem; Aamir Ali; Shagufta Naz; Muhammad Jamil; Naima Huma Naveed (Environmental Science and Pollution Research, 2022)

Sedimentology and diagenesis control on reservoir quality of Sheikhan Limestone (Eocene) at the Panoba and Sheikhan Nala Section, Kohat Basin, Pakistan - Atif Salim; Muhammad Kashif; Bin Dou; Danish Khan; Muhammad Jawad Munawar; Noor Ahmed; Naveed Rehman; Muhammad Sajid; Zahid Ullah; Muhammad Tariq (Carbonates and Evaporites, 2022)

A study of reservoir potential of Cretaceous–Paleocene successions of Nizampur basin, Khyber Pakhtunkhwa, Pakistan: constraints from fracture analysis, petrography and geochemistry - Muhammad Naveed Anjum; Abbas Ali Naseem; Muhammad Yaseen; Ali Hasnain; Junaid Khan; Jawad Ahmad (Carbonates and Evaporites, 2022)

Establishing a Green, Lean and Six Sigma implementation model for sustainable construction industry: an analysis of driving forces through ISM-MICMAC approach - Kramat Hussain; Zhen He; Naveed Ahmad; Muzaffar Iqbal; Muhammad Zubair Saeed (Environmental Science and Pollution Research, 2022)

First report of cucumber-infecting cucurbit chlorotic yellows virus (CCYV) associated with cucurbit yellows disease in Pakistan - Muhammad Nouman; Tahir Farooq; Rashida Parveen; Ummad ud-Din Umar; Muhammad Naveed Aslam; Mahmoud Moustafa; Muhammad Taimoor Shakeel (Journal of Plant Pathology, 2022)

First report of post-harvest brown spot of lemon caused by Alternaria alternata in Pakistan - Anam Moosa; Muhammad Naveed Aslam; Muhammad Taimoor Shakeel; Tanvir Ahmad; Mahmoud Moustafa; Mohammed Al-Shehri; Ahmed Al-Emam (Journal of Plant Pathology, 2022)

NGS-driven molecular diagnosis of heterogeneous hereditary neurological disorders reveals novel and known variants in disease-causing genes - Ayaz Khan; Shixiong Tian; Muhammad Tariq; Sheraz Khan; Muhammad Safeer; Naimat Ullah; Nazia Akbar; Iram Javed; Mahnoor Asif; Ilyas Ahmad; Shahid Ullah; Humayoon Shafique Satti; et al. (Molecular Genetics and Genomics, 2022)

Types, sources, socioeconomic impacts, and control strategies of environmental noise: a review - Zia Ur Rahman Farooqi; Iftikhar Ahmad; Allah Ditta; Predrag Ilic; Muhammad Amin; Abdul Basit Naveed; Aadil Gulzar (Environmental Science and Pollution Research, 2022)

Natural polysaccharide-based biodegradable polymeric platforms for transdermal drug delivery system: a critical analysis - Sobia Noreen; Jin-Xiang Ma; Muhammad Saeed; Fahad Pervaiz; Muhammad Farhan Hanif; Bilal Ahmed; Muhammad Irshad Farooq; Faizan Akram; Muhammad Safdar; Asadullah Madni; Muhammad Naveed; Li Chang-Xing (Drug Delivery and Translational Research, 2022)

Effects of climate change on vegetation and snow cover area in Gilgit Baltistan using MODIS data - Zulqarnain Satti; Muhammad Naveed; Muhammad Shafeeque; Sikandar Ali; Farkhod Abdullaev; Tauseef Muhammad Ashraf; Muhammad Irshad; Lanhai Li (Environmental Science and Pollution Research, 2022)

Assessment of Climate Change and Its Impacts on the Flows of a Subtropical River Basin in the Hindu-Kush Mountain, South Asia - Muhammad Naveed Anjum; Abdulnoor A. J. Ghanim; Hafiz Umar Farid; Muhammad Zaman; Usama Muhammad Niazi; Saif ur Rahman; Mabkhoot A. Alsaiari; Muhammad Irfan (Pure and Applied Geophysics, 2022)

Evaluation of histological post‐mortem changes in farmed Atlantic salmon ( Salmo salar L.) at different time intervals and storage temperatures - Lisa Furnesvik; Toni Erkinharju; Miroslava Hansen; Muhammad Naveed Yousaf; Tore Seternes (Journal of Fish Diseases, 2022)
The aim of this study was to evaluate histologic post‐mortem autolytic changes in farmed Atlantic salmon. The fish were either stored at room temperature (RT, 21°C), refrigerated (4°C) or frozen (−20°C), while fish necropsy was performed at 0, 1, 4, 24 and 48 h post‐storage (hps). In addition, gills were sampled at 0, 5, 10, 15, 30 and 45 min post‐storage (mps) at room temperature (RT). The haematoxylin and eosin‐stained tissue slides were evaluated and scored by using a semi‐quantitative scoring system. Our findings demonstrated gills and pyloric caeca/pancreas as the most severely autolysed organs while heart and skeletal musculature were least affected. Generally, moderate to severe autolysis appeared first at 4 hps, while severe changes were seen at 24 hps. Gills demonstrated autolytic changes as early as 10 mps and pyloric caeca/pancreas at 1 hps. Freezing did not prevent the autolysis and even contributed to freezing artefacts, which may lead to misdiagnosis. Keeping organs refrigerated slowed the autolytic progress within the first 4 hps marginally. This study recommends gills and pyloric caeca/pancreas should be sampled as early as possible, at least within 10 min post‐necropsy.

A novel lens of stock market capitalization and environmental degradation - Aamir Azeem; Muhammad Akram Naseem; Naveed Ul Hassan; Ijaz Butt; Muhammad Toseef Aslam; Shahid Ali; Atif khan Jadoon (Environmental Science and Pollution Research, 2022)

Correction to: Effect of eco‑friendly probiotics‑supplemented rapeseed meal–based diet on the performance of Catla catla fingerlings - Muhammad Mudassar Shahzad; Syed Makhdoom Hussain; Majid Hussain; Naveed Ahmad; Laraib Tahir; Kalsoom Akhtar (Environmental Science and Pollution Research, 2022)

Spatial green growth in China: exploring the positive role of investment in the treatment of industrial pollution - Muhammad Imran; Naveed Hayat; Muhammad Ali Saeed; Abdul Sattar; Salman Wahab (Environmental Science and Pollution Research, 2022)

Effect of eco-friendly probiotics-supplemented rapeseed meal–based diet on the performance of Catla catla fingerlings - Muhammad Mudassar Shahzad; Syed Makhdoom Hussain; Majid Hussain; Naveed Ahmad; Laraib Tahir; Kalsoom Akhtar (Environmental Science and Pollution Research, 2022)

Antidiarrheal and antispasmodic activities of Trillium govanianum rhizomes extract: involvement of calcium channel blockade - Naveed Muhammad; Shafiq Ur Rahman; Hilal Uddin; Omer Shehzad; Muhammad Ismail; Niaz Ali; Aslam Khan; Muhammad Shahid; Abid Ullah; Shujaat Ahmad; Haya Hussain; Ikram ul Haq; et al. (Natural Product Research, 2022)

Assessment of land use/land cover changes and its effect on land surface temperature using remote sensing techniques in Southern Punjab, Pakistan - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Hamid Majeed; Saeed Ahmad Qaisrani; Hafiz Mohkum Hammad; Muhammad Amjad; Iftikhar Ahmad; Shah Fahad; Naveed Ahmad; Wajid Nasim (Environmental Science and Pollution Research, 2022)

Molecular cloning, characterization and expression analysis of two 12-oxophytodienoate reductases (NtOPR1 and NtOPR2) from Nicotiana tabacum - Feiyan Huang; Farhat Abbas; Dylan O’Neill Rothenberg; Muhammad Imran; Sajid Fiaz; Naveed ur Rehman; Sikandar Amanullah; Afifa Younas; Yan Ding; Xianjie Cai; Xiaolong Chen; Lei Yu; et al. (Molecular Biology Reports, 2022)

Genome wide analysis of DWARF27 genes in soybean and functional characterization of GmD27c reveals eminent role of strigolactones in rhizobia interaction and nodulation in Glycine max - Naveed ur Rehman; Farhat Abbas; Muhammad Imran; Intikhab Alam; Muhammad Imran; Ihteram Ullah; Muhammad Riaz; Fahim Ullah Khan (Molecular Biology Reports, 2022)

RETRACTED ARTICLE: Novel acetamide derivatives of 2-aminobenzimidazole prevent inflammatory arthritis in rats via suppression of pro-inflammatory mediators - Aymun Madni Zubair; Muhammad Nasir Hayat Malik; Waqas Younis; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Alamgeer Yuchi; Muhammad Naveed Mushtaq; Romeeza Tahir; Muhammad Bilal Sarwar; Muhammad Roman; Ayaz Ali Khan; et al. (Inflammopharmacology, 2022)

Therapeutic potential of herbal medicine for the management of hyperlipidemia: latest updates - Abdur Rauf; Muhammad Akram; Hina Anwar; Muhammad Daniyal; Naveed Munir; Sami Bawazeer; Saud Bawazeer; Maksim Rebezov; Abdelhakim Bouyahya; Mohammad Ali Shariati; Muthu Thiruvengadam; Orynzhamal Sarsembenova; et al. (Environmental Science and Pollution Research, 2022)

Teratological effects of titanium dioxide nanoparticles in mice embryo - Munir Ahmad; Muhammad Khalil Ahmad Khan; Khurram Shahzad; Naveed Ahmad; Munazza Parveen; Muhammad Saleem Khan (Environmental Science and Pollution Research, 2022)

Development of Basmati lines by the introgression of three bacterial blight resistant genes through marker-assisted breeding - Allah Ditta Babar; Abha Zaka; Shahzad Amir Naveed; Niaz Ahmad; Kashif Aslam; Muhammad Asif; Umer Maqsood; Casiana M. Vera Cruz; Muhammad Arif (Euphytica, 2022)

Exogenous melatonin mitigates chromium toxicity in maize seedlings by modulating antioxidant system and suppresses chromium uptake and oxidative stress - Zaffar Malik; Sobia Afzal; Muhammad Dawood; Ghulam Hassan Abbasi; Muhammad Imran Khan; Muhammad Kamran; Mostafa Zhran; Malik Tahir Hayat; Muhammad Naveed Aslam; Muhammad Rafay (Environmental Geochemistry and Health, 2022)

Static force-based seismic analysis of reinforced concrete frames having weaker beam-column joints - Naveed Ahmad; Muhammad Rizwan; Qaisar Ali; Akhtar Naeem Khan (European Journal of Environmental and Civil Engineering, 2022)

Sub-lethal effects of organophosphates and synthetic pyrethroid insecticides on muscle tissue transaminases of Oreochromis niloticus in vivo - Muhammad Amin; Masarrat Yousuf; Naveed Ahmad; Mohammad Attaullah; Muhammad Ikram; Attia A. Abou Zaid; Clement Ameh Yaro; Eida M. Alshammari; Yaser S. Binnaser; Gaber El-Saber Batiha; Islam Dad Buneri (Toxicological Research, 2022)

Evaluation of combined utilization of marble dust powder and fly ash on the properties and sustainability of high-strength concrete - Zaryab Ahmed Rid; Syed Naveed Raza Shah; Muhammad Jaffar Memon; Ashfaque Ahmed Jhatial; Manthar Ali Keerio; Wan Inn Goh (Environmental Science and Pollution Research, 2022)

Triggering sustainable firm performance, supply chain competitive advantage, and green innovation through lean, green, and agile supply chain practices - Muhammad Waqas; Xue Honggang; Naveed Ahmad; Syed Abdul Rehman Khan; Zia Ullah; Muzaffar Iqbal (Environmental Science and Pollution Research, 2022)

Prevalence, epidemiology, seasonality, and phylogeny of Anaplasma marginale in blood samples of goats collected from Punjab, Pakistan - Muhammad Naveed Aziz; Muhammad Irfan; Asia Parveen; Muhammad Asif; Maryam Ijaz; Sadia Mumtaz; Sezayi Ozubek; Munir Aktas; Rana Khalid Iqbal; Furhan Iqbal (Tropical Animal Health and Production, 2022)

New organosulfur metallic compounds as potent drugs: synthesis, molecular modeling, spectral, antimicrobial, drug likeness and DFT analysis - Abrar Ul Hassan; Sajjad Hussain Sumrra; Muhammad Nadeem Zafar; Muhammad Faizan Nazar; Ehsan Ullah Mughal; Muhammad Naveed Zafar; Mazhar Iqbal (Molecular Diversity, 2022)

Twenty-first century hydrologic and climatic changes over the scarcely gauged Jhelum river basin of Himalayan region using SDSM and RCPs - Saira Munawar; Muhammad Naveed Tahir; Muhammad Hassan Ali Baig (Environmental Science and Pollution Research, 2022)

Establishing a corporate social responsibility implementation model for promoting sustainability in the food sector: a hybrid approach of expert mining and ISM–MICMAC - Muhammad Shahjahan Usmani; Jianling Wang; Naveed Ahmad; Zia Ullah; Muzaffar Iqbal; Muhammad Ismail (Environmental Science and Pollution Research, 2022)

Spatio-temporal variability of drought characteristics across Pakistan - Jae Eun Lee; Muhammad Azam; Saif Ur Rehman; Muhammad Waseem; M. Naveed Anjum; Arslan Afzal; M. J. M. Cheema; Muhammad Mehtab; Muhammad Latif; Rehan Ahmed; Muhammad Umar; Abid Sarwar; et al. (Paddy and Water Environment, 2022)

Anti-neuropathic pain activity of a cationic palladium (II) dithiocarbamate by suppressing the inflammatory mediators in paclitaxel-induced neuropathic pain model - Muhammad Naveed; Rahim Ullah; Adnan Khan; Bushra Shal; Ashraf Ullah Khan; Shahan Zeb Khan; Zia ur Rehman; Salman Khan (Molecular Biology Reports, 2021)

Paleostress inversion and outcrop fracture analysis of the brittle deformation along Main Boundary Thrust (MBT), NW Himalaya, Pakistan - Naveed Ahsan; Hassan Mehmood; Muhammad Armaghan Faisal Miraj; Iqra Bano; Abdul Qayyum; Rana Faizan Saleem (Journal of Earth System Science, 2021)

Correction to: First report of Alternaria alternata causing post‑harvest brown spot of Citrus reticulata Blanco cv. ‘Kinnow’ in Pakistan - Anam Moosa; Ayaz Farzand; Shahbaz Talib Sahi; Sajid Aleem Khan; Muhammad Naveed Aslam; Tanvir Ahmad; Ambreen Maqsood; Muhammad Shafique (Journal of Plant Pathology, 2021)

First report of Alternaria alternata causing post-harvest brown spot of Citrus reticulata Blanco cv. ‘Kinnow’ in Pakistan - Anam Moosa; Ayaz Farzand; Shahbaz Talib Sahi; Sajid Aleem Khan; Muhammad Naveed Aslam; Tanvir Ahmad; Ambreen Maqsood; Muhammad Shafique (Journal of Plant Pathology, 2021)

Trade, energy consumption, economic growth, and environmental quality: an empirical evidence from D-8 and G-7 countries - Muhammad Tariq Majeed; Naveed Asghar (Environmental Science and Pollution Research, 2021)

Characterization of Mercury-Resistant Rhizobacteria for Plant Growth Promotion: An In Vitro and In Silico Approach - Aatif Amin; Muhammad Naveed; Umair Munawar; Arslan Sarwar; Zakia Latif (Current Microbiology, 2021)

Comparative efficacy of Ovaprim and hMG (menotropin) to induce breeding in African catfish (Clarias gariepinus) - Muhammad Wajahat Ameer; Farhat Jabeen; Muhammad Asad; Ghazala Kaukab; Amnah Bashir; Misha Rasheed; Hafsa Younis; Naveed Munir; Javaria Nawaz; Rida Zainab; Muhammad Akram (Fish Physiology and Biochemistry, 2021)

Distance attenuation and local magnitude scale based on constant geometrical spreading in Northern Punjab, Pakistan - Mohammad Tahir; Ali Khan; Muhammad Naveed Mushtaq; Muhammad Tahir Iqbal; Talat Iqbal; Muhammad Ali Shah; Karam Khan; Riaz Ahmed Soomro (Acta Geophysica, 2021)

Nitrogen balance, production performance, and plasma metabolites of lactating buffaloes in response to varying dietary protein levels - Muhammad Uzair Akhtar; Hifzulrahman; Muhammad Imran; Talat Naseer Pasha; Anjum Khalique; Muhammad Saadullah; Muhammad Naeem Tahir; Muhammad Ikram-ul-Haq; Muhammad Naveed-ul-Haque (Tropical Animal Health and Production, 2021)

Processed animal manure improves morpho-physiological and biochemical characteristics of Brassica napus L. under nickel and salinity stress - Muhammad Naveed; Allah Ditta; Maryum Ahmad; Adnan Mustafa; Zulfiqar Ahmad; Manuel Conde-Cid; Shermeen Tahir; Syed Atizaz Ali Shah; Muhammad Mohsin Abrar; Shah Fahad (Environmental Science and Pollution Research, 2021)

Correction to: Tension-only ideal dissipative bracing for the seismic retrofit of precast industrial buildings - Bruno Dal Lago; Muhammad Naveed; Marco Lamperti Tornaghi (Bulletin of Earthquake Engineering, 2021)

Tension-only ideal dissipative bracing for the seismic retrofit of precast industrial buildings - Bruno Dal Lago; Muhammad Naveed; Marco Lamperti Tornaghi (Bulletin of Earthquake Engineering, 2021)
New precast frame industrial structures are seismically designed according to reliable modern criteria. However, most of the existing built stock hosting many workers and both regular and strategic industrial activities was designed and detailed neglecting the earthquake load or according to outdated seismic design criteria and regulations. Its seismic retrofit is a main challenge for the Engineering Community and a critical objective for institutional and private bodies. Among the envisaged solutions, the introduction of dissipative braces appears to be promising, although mostly inapplicable for these buildings, due to the brace lengths required by their typical large dimensions and the related proportioning against buckling. In this paper, an innovative seismic retrofitting technique based on monolateral dissipative bracing is investigated. The device proposed in this paper, yet in phase of preliminary design and testing, dissipates energy through friction in tension only while freely deforming in compression, which makes the issue related to compressive buckling irrelevant. A numerical analysis is carried out to investigate the efficiency of the proposed device in seismic retrofitting of precast industrial frame buildings with the aim to explore its feasibility and to better orient the definition of the slip threshold load range and the future development of the physical device. The simplified Capacity Spectrum Method (CSM) is employed for the global framing of the structural behaviour of the highly nonlinear retrofitted structures under seismic actions. A numerical tool is set to automatically apply the CSM based on the definition of few main parameters governing the seismic response of precast frame structures. The efficacy of the CSM is critically analysed through the comparison with the results of a set of nonlinear dynamic analyses. A smart simplified design process aimed at framing the most efficient threshold slip/yield load of the device given an existing structural configuration is presented with the application of the CSM through the identification of the most efficient performance indicator related to either displacement, shear force, equivalent dissipation of energy or a combination of them.

Low temperature and hypoxic conditions induce flavonoids biosynthesis and enhances antioxidant potential of crabapple (Malus profusion) fruits - Rana Naveed Ur Rehman; Sajid Ali; Mahmood Ul Hasan; Raheel Anwar; Muhammad Wasim Haider; Ahmad Sattar Khan; Aman Ullah Malik; Li Pengmin (Acta Physiologiae Plantarum, 2021)

RETRACTED ARTICLE: Pharmacological support to anti-arthritic prospective of physostigmine: a new approach - Haseeb Ahsan; Ihtisham Haider; Muhammad Naveed Mushtaq; Muhammad Naeem Qaisar; Farwa Naqvi; Awais Asif (Inflammopharmacology, 2021)

Sunlight-induced photocatalytic degradation of various dyes and bacterial inactivation using CuO–MgO–ZnO nanocomposite - Tauseef Munawar; Faisal Mukhtar; Sadaf Yasmeen; Muhammad Naveed-ur-Rehman; Muhammad Shahid Nadeem; Muhammad Riaz; Muhammad Mansoor; Faisal Iqbal (Environmental Science and Pollution Research, 2021)

Deteriorating Habitats and Conservation Strategies to Repopulate the Endangered Indus River Dolphin (Platanista gangetica minor); a Lesson Learned From the Conservation Practices of the Yangtze Finless Porpoise (Neophocaena asiaeorientalis) - Ghulam Nabi; Shahid Ahmad; Richard William McLaughlin; Yujiang Hao; Suliman Khan; Naveed Ahmad; Saeed Ahmad; Muhammad Shoaib Kiani; Yuefeng Wu; Dongming Li (Frontiers in Marine Science, 2021)
The Indus River dolphin (IRD; Platanista gangetica minor ) is an endangered and blind freshwater cetacean, endemic to the Indus River system of Pakistan and India. This review article provides detailed information about the major challenges IRDs are facing, and their possible consequences on the population dynamics of the IRD. Furthermore, we have suggested future conservation strategies for the IRD based on the lesson learned from the conservation of the Yangtze finless porpoise (YFP; Neophocaena asiaeorientalis ), a Critically Endangered freshwater cetacean. The major challenges for IRDs are habitat degradation, habitat fragmentation, and several types of industrial and agricultural pollutants. Worsening climatic changes, illegal fishing, and overfishing are additional threats. The construction of several barrages has fragmented the population into several short segments, some of which are too small for the IRDs to survive. In some segments, the population status of the IRD is unknown. In the remaining populations, genetic inbreeding, water shortage, canal entrapment, and altered ecological environment are potent negative factors for the survival of the IRD. Conservation strategies including fishing bans, translocation, and future research (tagging, periodic health assessments, necropsy and virtopsy, understanding the reproductive biology, and genomics) are possible recommendations. Very serious conservation efforts are needed to save the IRD from decline keeping in view the water shortage, pollution, lack of health assessment studies, and habitat degradation and fragmentation.

Long-term fertilization alters chemical composition and stability of aggregate-associated organic carbon in a Chinese red soil: evidence from aggregate fractionation, C mineralization, and 13C NMR analyses - Adnan Mustafa; Xu Hu; Syed Atizaz Ali Shah; Muhammad Mohsin Abrar; Ali Akbar Maitlo; Kashif Ali Kubar; Qudsia Saeed; Muhammad Kamran; Muhammad Naveed; Wang Boren; Sun Nan; Xu Minggang (Journal of Soils and Sediments, 2021)

Bismuth vanadate/MXene (BiVO4/Ti3C2) heterojunction composite: enhanced interfacial control charge transfer for highly efficient visible light photocatalytic activity - Muhammad Munir Sajid; Sadaf Bashir Khan; Yasir Javed; Nasir Amin; Zhengjun Zhang; Naveed Akhtar Shad; Haifa Zhai (Environmental Science and Pollution Research, 2021)

Sustainable construction through energy management practices in developing economies: an analysis of barriers in the construction sector - Muzaffar Iqbal; Junhai Ma; Naveed Ahmad; Kramat Hussain; Muhammad Shahjahan Usmani; Muneer Ahmad (Environmental Science and Pollution Research, 2021)

The electrophysiological effects of cannabidiol on action potentials and transmembrane potassium currents in rabbit and dog cardiac ventricular preparations - Leila Topal; Muhammad Naveed; Péter Orvos; Bence Pászti; János Prorok; Ákos Bajtel; Tivadar Kiss; Boglárka Csupor-Löffler; Dezső Csupor; István Baczkó; András Varró; László Virág; et al. (Archives of Toxicology, 2021)
Cannabis use is associated with known cardiovascular side effects such as cardiac arrhythmias or even sudden cardiac death. The mechanisms behind these adverse effects are unknown. The aim of the present work was to study the cellular cardiac electrophysiological effects of cannabidiol (CBD) on action potentials and several transmembrane potassium currents, such as the rapid (I Kr ) and slow (I Ks ) delayed rectifier, the transient outward (I to ) and inward rectifier (I K1 ) potassium currents in rabbit and dog cardiac preparations. CBD increased action potential duration (APD) significantly in both rabbit (from 211.7 ± 11.2. to 224.6 ± 11.4 ms, n = 8) and dog (from 215.2 ± 9.0 to 231.7 ± 4.7 ms, n = 6) ventricular papillary muscle at 5 µM concentration. CBD decreased I Kr , I Ks and I to (only in dog) significantly with corresponding estimated EC 50 values of 4.9, 3.1 and 5 µM, respectively, without changing I K1 . Although the EC 50 value of CBD was found to be higher than literary C max values after CBD smoking and oral intake, our results raise the possibility that potassium channel inhibition by lengthening cardiac repolarization might have a role in the possible proarrhythmic side effects of cannabinoids in situations where CBD metabolism and/or the repolarization reserve is impaired.

Phenolic, flavonoid content and radical scavenging activity of Smilax china with its inhibitory potential against clinically important enzymes - Hafiz Ibtesam Ahmad; Haji Muhammad Shoaib Khan; Naveed Akhtar; Shakeel Ijaz (Natural Product Research, 2021)

RETRACTED ARTICLE: Bi-polymeric Spongy Matrices Through Cross-linking Polymerization: Synthesized and Evaluated for Solubility Enhancement of Acyclovir - Saima Asghar; Naveed Akhtar; Muhammad Usman Minhas; Kifayat Ullah Khan (AAPS PharmSciTech, 2021)

Integrated Approach for Inventories and Quantitative Assessment of Geological and Paleontological Sites from Precambrian to Quaternary Successions in the Salt Range, Pakistan - Muhammad Yaseen; Abbas Ali Naseem; Jawad Ahmad; Mubashir Mehmood; Muhammad Naveed Anjum (Geoheritage, 2021)

Mapping green technologies literature published between 1995 and 2019: a scientometric review from the perspective of the manufacturing industry - Muhammad Shahjahan Usmani; Jianling Wang; Naveed Ahmad; Muzaffar Iqbal; Rahil Irfan Ahmed (Environmental Science and Pollution Research, 2021)

Effect of feeding calcium propionate supplemented cotton seed cake on milk yield, milk composition and aflatoxin concentration in lactating buffaloes - Murtaza Ali Tipu; Anjum Khalique; Muhammad Naveed-ul-Haque; Muhammad Qamer Shahid; Maqsood Akhtar; Mubashir Ilyas (Tropical Animal Health and Production, 2021)

Treatment of Wilms’ nephroblastoma cancer cells via EGFR targeting of dactinomycin loaded DNA-nanowires - Mirza Muhammad Faran Ashraf Baig; Chengfei Zhang; Muhammad Furqan Akhtar; Ammara Saleem; Naveed Nisar (Journal of Pharmaceutical Investigation, 2021)

Temporal Analysis for Detection of Anomalies in Precipitation Patterns over a Selected Area in the Indus Basin of Pakistan - Akhtar Ali; Hafiz Umar Farid; Zahid Mehmood Khan; Ijaz Ahmad; Muhammad Naveed Anjum; Muhammad Mubeen; Aamir Shakoor (Pure and Applied Geophysics, 2021)

Field application of allelopathic bacteria to control invasion of little seed canary grass in wheat - Tasawar Abbas; Zahir Ahmad Zahir; Muhammad Naveed (Environmental Science and Pollution Research, 2021)

Tectonic evolution, prospectivity and structural studies of the hanging wall of Main Boundary Thrust along Akhurwal-Kohat transect, Khyber Pakhtunkhwa: implications for future exploration - Muhammad Yaseen; Sohail Wahid; Sajjad Ahmad; Gohar Rehman; Jawad Ahmad; Muhammad Naveed Anjum; Mubashir Mehmood (Arabian Journal of Geosciences, 2021)

Influence of tourism, governance, and foreign direct investment on energy consumption and CO2 emissions: a panel analysis of Muslim countries - Faqeer Muhammad; Anwar Khan; Naveed Razzaq; Rehmat Karim (Environmental Science and Pollution Research, 2021)

Factors Influencing Sleep Quality and Effects of Sleep on Hypertension - Ali Asghar Mirjat; Ali Akbar Mirjat; Muhammad Naveed; Fatima Majeed; Shen Chong (Sleep and Vigilance, 2020)

Synthetic β-hydroxy ketone derivative inhibits cholinesterases, rescues oxidative stress and ameliorates cognitive deficits in 5XFAD mice model of AD - Syed Ilyas Ahmad; Gowhar Ali; Tahir Muhammad; Rahim Ullah; Muhammad Naveed Umar; Aisha Nasir Hashmi (Molecular Biology Reports, 2020)

Zinc Application in Combination with Zinc Solubilizing Enterobacter sp. MN17 Improved Productivity, Profitability, Zinc Efficiency, and Quality of Desi Chickpea - Aman Ullah; Muhammad Farooq; Faisal Nadeem; Abdul Rehman; Mubshar Hussain; Ahmad Nawaz; Muhammad Naveed (Journal of Soil Science and Plant Nutrition, 2020)

Optimizing Boron Seed Coating Level and Boron-Tolerant Bacteria for Improving Yield and Biofortification of Chickpea - Mubshar Hussain; Noman Mehboob; Muhammad Naveed; Kousar Shehzadi; Tauqeer Ahmad Yasir (Journal of Soil Science and Plant Nutrition, 2020)

Combined application of Bacillus sp. MN-54 and phosphorus improved growth and reduced lead uptake by maize in the lead-contaminated soil - Muhammad Junaid Afzal; Muhammad Imran Khan; Sardar Alam Cheema; Saddam Hussain; Muhammad Anwar-ul-Haq; Muhammad Hayder Ali; Muhammad Naveed (Environmental Science and Pollution Research, 2020)

Quantification and risk assessment of heavy metal build-up in soil–plant system after irrigation with untreated city wastewater in Vehari, Pakistan - Tania Sarwar; Muhammad Shahid; Natasha; Sana Khalid; Ali Haidar Shah; Naveed Ahmad; Muhammad Asif Naeem; Zia ul Haq; Behzad Murtaza; Hafiz Faiq Bakhat (Environmental Geochemistry and Health, 2020)

The Relevance of SNPs at 3′UTR Region of CASP7 and miR-371b-5p Associated Diseases: A Computational Analysis - Muhammad Safdar; Sana Zaheer; Rozhgar A. Khailany; Sadaf Parvez; Muhammad Naveed; Piplu Bhuiyan; Mehmet Ozaslan; Rebaz Moatasam; Mustafa S. Al-Attar; Musarrat Abbas Khan; Yasmeen Junejo (Cell Biochemistry and Biophysics, 2020)

Effect of increasing pre-pubertal concentrate levels on reproductive and lactation performance of Nili-Ravi Buffalo heifers - Muhammad Saadullah; Zeeshan Muhammad Iqbal; Muhammad Naveed-ul-Haque; Hifzulrahman; Jalees Ahmed Bhatti; Muhammad Abdullah (Tropical Animal Health and Production, 2020)

Partial Substitution of Fishmeal with Plant Protein Source the Soybean Meal in the Diets of Arabian Yellowfin Seabream Acanthopagrus arabicus Juveniles - Naveed Ahmad; Jamal Pirzada A. Siddiqui; Ghulam Nabi; Khan Mir Khan; Amjad Ali; Yasmeen Zamir; Mohammad Abdul Momin Siddique; Shabir Ali Amir; Farah Naz Khokhar; Muhammad Amin (Thalassas: An International Journal of Marine Sciences, 2020)

RETRACTED ARTICLE: The integrin facilitated internalization of fibronectin-functionalized camptothecin-loaded DNA-nanofibers for high-efficiency anticancer effects - Mirza Muhammad Faran Ashraf Baig; Wing-Fu Lai; Saba Ashraf; Ammara Saleem; Muhammad Furqan Akhtar; Reyaj Mikrani; Muhammad Naveed; Farhan Siddique; Abdoh Taleb; Jahanzeb Mudassir; Ghulam Jilany Khan; Muhammad Tayyab Ansari (Drug Delivery and Translational Research, 2020)

Pharmacokinetic Advantage of ASD Device Promote Drug Absorption through the Epicardium - Reyaj Mikrani; Cunyu Li; Muhammad Naveed; Cuican Li; Mirza Muhammad Faran Ashraf Baig; Qin Zhang; Yue Wang; Juanjuan Peng; Lingzhi Zhao; Xiaohui Zhou (Pharmaceutical Research, 2020)

Integrated Application of Organic Amendments with Alcaligenes sp. AZ9 Improves Nutrient Uptake and Yield of Maize (Zea mays) - Azhar Hussain; Maqshoof Ahmad; Muhammad Zahid Mumtaz; Sajjad Ali; Rubab Sarfraz; Muhammad Naveed; Moazzam Jamil; Christos A. Damalas (Journal of Plant Growth Regulation, 2020)

The engineering assessments and potential aggregate analysis of mesozoic carbonates of Kohat Hills Range, KP, Pakistan - Gohar Rehman; Guangcheng Zhang; Maqsood Ur Rahman; Naveed Ur Rahman; Tariq Usman; Muhammad Imraz (Acta Geodaetica et Geophysica, 2020)

RETRACTED ARTICLE: Matrine alleviates neurobehavioral alterations via modulation of JNK-mediated caspase-3 and BDNF/VEGF signaling in a mouse model of burn injury - Adnan Khan; Bushra Shal; Muhammad Naveed; Bakht Nasir; Nadeem Irshad; Hussain Ali; Salman Khan (Psychopharmacology, 2020)

First report of brown leaf spot of rice caused by Curvularia spicifera in Pakistan - Hafiz Muhammad Usman Aslam; Safdar Ali; Muhammad Atiq; Muhammad Zeeshan Mansha; Hafiz Muhammad Aatif; Hafiz Arslan Anwaar; Khalid Naveed (Journal of Plant Pathology, 2020)

Determination of oil contents from eight varieties of olea europaea (Olive) grown in Pakistan - Abdul Khaliq; Syed Muhammad Ali Shah; Muhammad Akram; Naveed Munir; Muhammad Daniyal; Muhammad Irshad; Saeed Ahmad (Natural Product Research, 2020)

Protein kinase CK2 impact on intracellular calcium homeostasis in prostate cancer - Muhammad Afzal; Betsy T. Kren; A. Khaliq Naveed; Janeen H. Trembley; Khalil Ahmed (Molecular and Cellular Biochemistry, 2020)

Vibration analysis of damaged and undamaged steel structure systems: cantilever column and frame - Muhammad Abuzar Khan; Kareem Akhtar; Naveed Ahmad; Feroz Shah; Naeem Khattak (Earthquake Engineering and Engineering Vibration, 2020)

RETRACTED ARTICLE: Poloxamer-407-Co-Poly (2-Acrylamido-2-Methylpropane Sulfonic Acid) Cross-linked Nanogels for Solubility Enhancement of Olanzapine: Synthesis, Characterization, and Toxicity Evaluation - Kifayat Ullah Khan; Naveed Akhtar; Muhammad Usman Minhas (AAPS PharmSciTech, 2020)

Synthesis of Ligand Functionalized ErbB-3 Targeted Novel DNA Nano-Threads Loaded with the Low Dose of Doxorubicin for Efficient In Vitro Evaluation of the Resistant Anti-Cancer Activity - Mirza Muhammad Faran Ashraf Baig; Wing-Fu Lai; Anam Ahsan; Mehreen Jabeen; Muhammad Asim Farooq; Reyaj Mikrani; Muhammad Abbas; Muhammad Naveed; Said Abasse Kassim; Faisal Raza; Afzal Ahmed Dar; Muhammad Tayyab Ansari (Pharmaceutical Research, 2020)

Organochlorine pesticides in the surrounding soils of POPs destruction facility: source fingerprinting, human health, and ecological risks assessment - Syeda Nazish Ali; Mujtaba Baqar; Mehvish Mumtaz; Uzma Ashraf; Muhammad Naveed Anwar; Abdul Qadir; Sajid Rashid Ahmad; Abdul-Sattar Nizami; Huang Jun (Environmental Science and Pollution Research, 2020)

Temperature trends and elevation dependent warming during 1965–2014 in headwaters of Yangtze River, Qinghai Tibetan Plateau - Naveed Ahmed; Gen-xu Wang; Adeyeri Oluwafemi; Sarfraz Munir; Zhao-yong Hu; Aamir Shakoor; Muhammad Ali Imran (Journal of Mountain Science, 2020)

An epicardial delivery of nitroglycerine by active hydraulic ventricular support drug delivery system improves cardiac function in a rat model - Xue Li; Reyaj Mikrani; Cunyu Li; Muhammad Naveed; Ziwei Liu; Muhammad Abbas; Yijie Cheng; Lei Han; Zhijie Wang; Xiaohui Zhou (Drug Delivery and Translational Research, 2020)

Delineation of regional groundwater vulnerability using DRASTIC model for agricultural application in Pakistan - Aamir Shakoor; Zahid M. Khan; Hafiz U. Farid; Muhammad Sultan; Ijaz Ahmad; Naveed Ahmad; Muhammad H. Mahmood; Muhammad U. Ali (Arabian Journal of Geosciences, 2020)

3D-Deep Learning Based Automatic Diagnosis of Alzheimer’s Disease with Joint MMSE Prediction Using Resting-State fMRI - Nguyen Thanh Duc; Seungjun Ryu; Muhammad Naveed Iqbal Qureshi; Min Choi; Kun Ho Lee; Boreom Lee (Neuroinformatics, 2020)

A Novel Approach to Evaluate, Highlight, and Conserve the Geologically Significant Geoheritage Sites from the Peshawar Basin, Khyber Pakhtunkhwa, Pakistan: Insights into Their Geoscientific, Educational, and Social Importance - Muhammad Yaseen; Mukhtiar Ghani; Muhammad Naveed Anjum; Muhammad Sajid; Irfan Ullah Jan; Mubbashir Mehmood; Emad Ullah; Waqas Muzaffir (Geoheritage, 2019)

Numerical investigation of the flow characteristics through discontinuous and layered vegetation patches of finite width in an open channel - Usman Ghani; Naveed Anjum; Ghufran Ahmed Pasha; Muhammad Ahmad (Environmental Fluid Mechanics, 2019)

Anti-pollution cosmetic-based one-step formation of w/o/w multiple emulsion containing D-biotin for skin protection: fabrication and in vitro and in vivo evaluation - Atif Ali; Sajid Iqbal; Aqsa Ilyas; Hira Khan; Muhammad Hassham Hassan Bin Asad; Nighat Fatima; Naveed Akhtar (Drug Delivery and Translational Research, 2019)

Potential nutraceutical and food additive properties and risks of coffee: a comprehensive overview - Muhammad Saeed; Muhammad Naveed; Jannat BiBi; Asghar Ali Kamboh; Lucas Phil; Sun Chao (Critical Reviews in Food Science and Nutrition, 2019)

Effect of feeding different levels of discarded date palm (Phoenix dactylifera) on digestibility, milk yield, and composition in Damani sheep - Naveed Iqbal; Muhammad Tahir Khan; Haq Amanullah; Israru Din; Hamayun Khan; Muqader Shah; Muhammad Mushtaq (Tropical Animal Health and Production, 2019)

A cross-sectional study of methicillin-resistant Staphylococcus aureus at the equine-human interface - Namra Waqar; Quratulain Amin; Tariq Munir; Muhammad Sohaib Ikram; Naveed Shahzad; Arkim Mirza; Arshad Ali; Muhammad Imran Arshad (Tropical Animal Health and Production, 2019)

RETRACTED ARTICLE: A new cationic palladium(II) dithiocarbamate exhibits anti-inflammatory, analgesic, and antipyretic activities through inhibition of inflammatory mediators in in vivo models - Muhammad Naveed; Shahan Zeb Khan; Sara Zeeshan; Adnan Khan; Bushra Shal; Ayesha Atiq; Hussain Ali; Rahim Ullah; Zia-ur-Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

First report of Geotrichum candidum causing postharvest sour rot of carrot in Punjab, Pakistan - Akhtar Hameed; Muhammad Waqar Alam; Abdul Rehman; Khalid Naveed; Muhammad Atiq; Nasir Ahmed Rajput; Sohaib Sarfraz; Nadia Liaqat; Faizan Ahmad Tahir (Journal of Plant Pathology, 2019)

N-Pyrazoloyl and N-thiopheneacetyl hydrazone of isatin exhibited potent anti-inflammatory and anti-nociceptive properties through suppression of NF-κB, MAPK and oxidative stress signaling in animal models of inflammation - Sara Zeeshan; Muhammad Naveed; Adnan Khan; Ayesha Atiq; Maryam Arif; Muhammad Naeem Ahmed; Yeong Shik Kim; Salman Khan (Inflammation Research, 2019)

Haunch retrofitting technique for seismic upgrading deficient RC frames - Naveed Ahmad; Junaid Akbar; Muhammad Rizwan; Bashir Alam; Akhtar Naeem Khan; Abdul Lateef (Bulletin of Earthquake Engineering, 2019)

Quantification of spatial temporal variability of snow cover and hydro-climatic variables based on multi-source remote sensing data in the Swat watershed, Hindukush Mountains, Pakistan - Muhammad Naveed Anjum; Yongjian Ding; Donghui Shangguan; Junguo Liu; Ijaz Ahmad; Muhammad Wajid Ijaz; Muhammad Imran Khan (Meteorology and Atmospheric Physics, 2019)

Variants in KIAA0825 underlie autosomal recessive postaxial polydactyly - Irfan Ullah; Naseebullah Kakar; Isabelle Schrauwen; Shabir Hussain; Imen Chakchouk; Khurram Liaqat; Anushree Acharya; Naveed Wasif; Regie Lyn P. Santos-Cortez; Saadullah Khan; Abdul Aziz; Kwanghyuk Lee; et al. (Human Genetics, 2019)

Development of local magnitude scale for the Northern Punjab, Pakistan - Muhammad Naveed Mushtaq; Muhammd Tahir; Muhammd Ali Shah; Fehmeeda Khanam (Journal of Seismology, 2019)

Evaluation of SWAT Model performance on glaciated and non-glaciated subbasins of Nam Co Lake, Southern Tibetan Plateau, China - Muhammad Adnan; Shi-change Kang; Guo-shuai Zhang; Muhammad Naveed Anjum; Muhammad Zaman; Yu-qing Zhang (Journal of Mountain Science, 2019)

Prevalence and current therapy in chronic liver disorders - Muhammad Daniyal; Muhammad Akram; Rida Zainab; Naveed Munir; Aamir Sharif; Syed Muhammad Ali Shah; Bin Liu; Wei Wang (Inflammopharmacology, 2019)

Combined use of biochar and zinc oxide nanoparticle foliar spray improved the plant growth and decreased the cadmium accumulation in rice (Oryza sativa L.) plant - Shafaqat Ali; Muhammad Rizwan; Shamaila Noureen; Sarwat Anwar; Basharat Ali; Muhammad Naveed; Elsayed Fathi Abd_Allah; Abdulaziz A. Alqarawi; Parvaiz Ahmad (Environmental Science and Pollution Research, 2019)

The Asian Houbara Bustard (Chlamydotis macqueenii): on an accelerating path to extinction? - Ghulam Nabi; Rahim Ullah; Suliman Khan; Nawsherwan; Muhammad Amin; Naveed Rauf (Biodiversity and Conservation, 2019)

pH/Thermo-Dual Responsive Tunable In Situ Cross-Linkable Depot Injectable Hydrogels Based on Poly(N-Isopropylacrylamide)/Carboxymethyl Chitosan with Potential of Controlled Localized and Systemic Drug Delivery - Samiullah Khan; Naveed Akhtar; Muhammad Usman Minhas; Syed Faisal Badshah (AAPS PharmSciTech, 2019)

Folate-Functionalized Thiomeric Nanoparticles for Enhanced Docetaxel Cytotoxicity and Improved Oral Bioavailability - Muhammad Sajjad; Muhammad Imran Khan; Sara Naveed; Sana Ijaz; Omer Salman Qureshi; Syed Atif Raza; Gul Shahnaz; Muhammad Farhan Sohail (AAPS PharmSciTech, 2019)

Yucca schidigera can mitigate ammonia emissions from manure and promote poultry health and production - Muhammad Saeed; Muhammad Asif Arain; Muhammad Naveed; Mahmoud Alagawany; Mohamed Ezzat Abd El-Hack; Zohaib Ahmed Bhutto; Marek Bednarczyk; Mohib Ullah Kakar; Mervat Abdel-Latif; Sun Chao (Environmental Science and Pollution Research, 2018)

Bioremediation of tannery effluent by Cr- and salt-tolerant bacterial strains - Sobia Ashraf; Muhammad Naveed; Muhammad Afzal; Sana Ashraf; Khadeeja Rehman; Azhar Hussain; Zahir Ahmad Zahir (Environmental Monitoring and Assessment, 2018)

Effect of distillery spentwash fertigation on crop growth, yield, and accumulation of potentially toxic elements in rice - Sadiq Naveed; Abdur Rehim; Muhammad Imran; Muhammad Faraz Anwar; Saddam Hussain (Environmental Science and Pollution Research, 2018)

Hydrocarbon source rock potential evaluation of the Late Paleocene Patala Formation, Salt Range, Pakistan: Organic geochemical and palynofacies approach - Nasar Khan; Naveed Anjum; Mansoor Ahmad; Muhammad Awais; Naqib Ullah (Journal of Earth System Science, 2018)

Seismic fragility functions for code compliant and non-compliant RC SMRF structures in Pakistan - Naveed Ahmad; Asif Shahzad; Qaisar Ali; Muhammad Rizwan; Akhtar Naeem Khan (Bulletin of Earthquake Engineering, 2018)

Strategic use of water: a step toward cadmium-free basmati rice (Oryza sativa L.) - Muhammad Naveed; Saifullah; Umair Riaz; Ghulam Murtaza; Sadia Bibi; Ammara Arooj; Qamar uz Zaman (Paddy and Water Environment, 2018)

Exogenously applied zinc and copper mitigate salinity effect in maize (Zea mays L.) by improving key physiological and biochemical attributes - Muhammad Naveed Iqbal; Rizwan Rasheed; Muhammad Yasin Ashraf; Muhammad Arslan Ashraf; Iqbal Hussain (Environmental Science and Pollution Research, 2018)

Effects of increasing dietary protein supplies on milk yield, milk composition, and nitrogen use efficiency in lactating buffalo - Muhammad Naveed-ul-Haque; Muhammad Uzair Akhtar; Rizwan Munnawar; Saba Anwar; Anjum Khalique; Murtaza Ali Tipu; Fayyaz Ahmad; Muhammad Qamer Shahid (Tropical Animal Health and Production, 2018)

Correction to: Pre-existing Small Vessel Disease in Patients with Acute Stroke from the Middle East, Southeast Asia, and Philippines - Naveed Akhtar; Abdul Salam; Saadat Kamran; Atlantic D’Souza; Yahia Imam; Pablo Garcia Bermejo; Muhammad Faisal Wadiwala; Ahmed Own; Ahmed ElSotouhy; Surjith Vattoth; Paula Bourke; Zain Bhutta; et al. (Translational Stroke Research, 2018)

Potential impacts of climate change and adaptation strategies for sunflower in Pakistan - Muhammad Awais; Aftab Wajid; Muhammad Farrukh Saleem; Wajid Nasim; Ashfaq Ahmad; Muhammad Aown Sammar Raza; Muhammad Usman Bashir; Muhammad Mubeen; Hafiz Mohkum Hammad; Muhammad Habib ur Rahman; Umer Saeed; Muhammad Naveed Arshad; et al. (Environmental Science and Pollution Research, 2018)

Biodegradable Ingredient-Based Emulgel Loaded with Ketoprofen Nanoparticles - Rabia Gul; Naveed Ahmed; Naseem Ullah; Muhammad Ijaz Khan; Abdelhamid Elaissari; Asim.ur. Rehman (AAPS PharmSciTech, 2018)

Efficiency of biogas slurry and Burkholderia phytofirmans PsJN to improve growth, physiology, and antioxidant activity of Brassica napus L. in chromium-contaminated soil - Muhammad Nafees; Shafaqat Ali; Muhammad Naveed; Muhammad Rizwan (Environmental Science and Pollution Research, 2018)

Application of gravity and magnetic methods for the crustal study and delineating associated ores in the western limb of Hazara Kashmir Syntaxis, Northwest Himalayas, Pakistan - Muhammad Rustam Khan; Shahid Saleem Bilali; Fahad Hameed; Awais Rabnawaz; Sohail Mustafa; Naveed Azad; Muhammad Basharat; Abrar Niaz (Arabian Journal of Geosciences, 2018)

Assessment of Air Temperature Trends in the Source Region of Yellow River and Its Sub-Basins, China - Mudassar Iqbal; Jun Wen; Xin Wang; Yongchao Lan; Hui Tian; Muhammad Naveed Anjum; Muhammad Adnan (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Combined Applications of Aminoethoxyvinylglycine with Salicylic Acid or Nitric Oxide Reduce Oxidative Stress in Peach During Ripening and Cold Storage - Mohammad Javed Tareen; Zora Singh; Ahmad Sattar Khan; Nadeem Akhtar Abbasi; Muhammad Naveed (Journal of Plant Growth Regulation, 2017)

Assessment of resistance to bacterial wilt incited by Ralstonia solanacearum in tomato germplasm - Muhammad Naveed Aslam; Tariq Mukhtar; Muhammad Arshad Hussain; Muhammad Raheel (Journal of Plant Diseases and Protection, 2017)

Evaluation of Green Waste and Popular Twigs Biochar Produced at Low and High Pyrolytic Temperature for Efficient Removal of Metals from Water - Zeshan Aslam; Muhammad Khalid; Muhammad Naveed; Muhammad Shahid; Muhammad Aon (Water, Air, & Soil Pollution, 2017)

Reconsidering betaine as a natural anti-heat stress agent in poultry industry: a review - Muhammad Saeed; Daryoush Babazadeh; Muhammad Naveed; Muhammad Asif Arain; Faiz Ul Hassan; Sun Chao (Tropical Animal Health and Production, 2017)

Bioherbicidal activity of allelopathic bacteria against weeds associated with wheat and their effects on growth of wheat under axenic conditions - Tasawar Abbas; Zahir Ahmad Zahir; Muhammad Naveed (BioControl, 2017)

Nitrogen and plant population change radiation capture and utilization capacity of sunflower in semi-arid environment - Muhammad Awais; Aftab Wajid; Muhammad Usman Bashir; Muhammad Habib-ur-Rahman; Muhammad Aown Sammar Raza; Ashfaq Ahmad; Muhammad Farrukh Saleem; Hafiz Mohkum Hammad; Muhammad Mubeen; Umer Saeed; Muhammad Naveed Arshad; Shah Fahad; et al. (Environmental Science and Pollution Research, 2017)

Biological control of broad-leaved dock infestation in wheat using plant antagonistic bacteria under field conditions - Tasawar Abbas; Zahir Ahmad Zahir; Muhammad Naveed; Zubair Aslam (Environmental Science and Pollution Research, 2017)

Formulation and In Vitro Characterization of Thiolated Buccoadhesive Film of Fluconazole - Kiran Naz; Gul Shahnaz; Naveed Ahmed; Naveeda Akhtar Qureshi; Hafiz Shoaib Sarwar; Muhammad Imran; Gul Majid Khan (AAPS PharmSciTech, 2017)

CDK5RAP2 interaction with components of the Hippo signaling pathway may play a role in primary microcephaly - Salil K. Sukumaran; Maria Stumpf; Sarah Salamon; Ilyas Ahmad; Kurchi Bhattacharya; Sarah Fischer; Rolf Müller; Janine Altmüller; Birgit Budde; Holger Thiele; Muhammad Tariq; Naveed Altaf Malik; et al. (Molecular Genetics and Genomics, 2017)

Examination of CK2α and NF-κB p65 expression in human benign prostatic hyperplasia and prostate cancer tissues - Fatima Qaiser; Janeen H. Trembley; Sarah Sadiq; Iqbal Muhammad; Rubina Younis; Shoaib Naiyar Hashmi; Badar Murtaza; Thomas S. Rector; Abdul Khaliq Naveed; Khalil Ahmed (Molecular and Cellular Biochemistry, 2016)

Molecular characterization of infectious bursal disease viruses from Pakistan - Muhammad Zubair Shabbir; Muhammad Ali; Muhammad Abbas; Umer Naveed Chaudhry; Zia-ur-Rehman; Muhammad Munir (Archives of Virology, 2016)

Relationship between in vitro characterization and comparative efficacy of plant growth-promoting rhizobacteria for improving cucumber salt tolerance - Sajid Mahmood Nadeem; Maqshoof Ahmad; Muhammad Naveed; Muhammad Imran; Zahir Ahmad Zahir; David E. Crowley (Archives of Microbiology, 2016)

Fault-controlled, bedding-parallel dolomite in the middle Jurassic Samana Suk Formation in Margalla Hill Ranges, Khanpur area (North Pakistan): petrography, geochemistry, and petrophysical characteristics - Mumtaz Muhammad Shah; Waqar Ahmed; Naveed Ahsan; Mona Lisa (Arabian Journal of Geosciences, 2016)

Synergism of polyamines and plant growth regulators enhanced morphogenesis, stevioside content, and production of commercially important natural antioxidants in Stevia rebaudiana Bert - Shahid Akbar Khalil; Nasir Kamal; Muhammad Sajid; Nisar Ahmad; Roshan Zamir; Naveed Ahmad; Shahid Ali (In Vitro Cellular & Developmental Biology - Plant, 2016)

Antimicrobial and inhibition on heat-induced protein denaturation of constituents isolated from Polygonatum verticillatum rhizomes - Haroon Khan; Muhammad Saeed; Abdur Rauf; Muhammad Atif Khan; Naveed Muhammad (Natural Product Research, 2015)

First evidence of the analgesic activity of govaniadine, an alkaloid isolated from Corydalis govaniana Wall. - Naveed Muhammad; Ram Lal Shrestha; Achyut Adhikari; Abdul Wadood; Haroon Khan; Amir Zada Khan; Francesco Maione; Nicola Mascolo; Vincenzo De Feo (Natural Product Research, 2015)

Observed damages in Pakistan due to 16 April 2013 Iran earthquake - Muhammad Masood Rafi; Sarosh H. Lodi; Muhammad Ahmed; Naveed Alam (Bulletin of Earthquake Engineering, 2015)

Cadmium-tolerant bacteria induce metal stress tolerance in cereals - Iftikhar Ahmad; Muhammad Javed Akhtar; Zahir Ahmad Zahir; Muhammad Naveed; Birgit Mitter; Angela Sessitsch (Environmental Science and Pollution Research, 2014)

The endophyte Enterobacter sp. FD17: a maize growth enhancer selected based on rigorous testing of plant beneficial traits and colonization characteristics - Muhammad Naveed; Birgit Mitter; Sohail Yousaf; Milica Pastar; Muhammad Afzal; Angela Sessitsch (Biology and Fertility of Soils, 2014)

The diversity of Rhizobia, Sinorhizobia and novel non-Rhizobial Paenibacillus nodulating wild herbaceous legumes - Sadia Latif; SamiUllah Khan; Muhammad Naveed; Ghulam Mustafa; Tasmia Bashir; Abdul Samad Mumtaz (Archives of Microbiology, 2013)

Isolation of long-chain esters from the rhizome of Polygonatum verticillatum by potent tyrosinase inhibition - Haroon Khan; Muhammad Saeed; Murad Ali Khan; Izhar-ul-Haq; Naveed Muhammad; Rukhsana Ghaffar (Medicinal Chemistry Research, 2013)

Evaluation of n-hexane extract of Viola betonicifolia for its neuropharmacological properties - Naveed Muhammad; Muhammad Saeed; Haroon Khan; Ikramul Haq (Journal of Natural Medicines, 2013)

Antimalarial and free radical scavenging activities of rhizomes of Polygonatum verticillatum supported by isolated metabolites - Haroon Khan; Muhammad Saeed; Murad Ali Khan; Inamullah Khan; Manzoor Ahmad; Naveed Muhammad; Afsar Khan (Medicinal Chemistry Research, 2012)

Comparative effectiveness of Pseudomonas and Serratia sp. containing ACC-deaminase for coinoculation with Rhizobium leguminosarum to improve growth, nodulation, and yield of lentil - Zahir Ahmad Zahir; Muhammad Zafar-ul-Hye; Saima Sajjad; Muhammad Naveed (Biology and Fertility of Soils, 2011)

Novel mutations in the keratin-74 (KRT74) gene underlie autosomal dominant woolly hair/hypotrichosis in Pakistani families - Naveed Wasif; Syed Kamran ul-Hassan Naqvi; Sulman Basit; Nadir Ali; Muhammad Ansar; Wasim Ahmad (Human Genetics, 2011)

Assessment of genetic variability among selected species of Apocynaceae - Tariq Mahmood; Anna Iqbal; Nazia Nazar; Ishrat Naveed; Bilal Haider Abbasi; Syed Muhammad Saqlan Naqvi (Biologia, 2011)

Dynamics of resistance to organophosphate and carbamate insecticides in the cotton whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) from Pakistan - Mushtaq Ahmad; M. Iqbal Arif; Muhammad Naveed (Journal of Pest Science, 2010)

Genetic mapping of a novel hypotrichosis locus to chromosome 7p21.3–p22.3 in a Pakistani family and screening of the candidate genes - Sulman Basit; Ghazanfar Ali; Naveed Wasif; Muhammad Ansar; Wasim Ahmad (Human Genetics, 2010)

Phylogenetic analysis of Bemisia tabaci (Hemiptera: Aleyrodidae) populations from cotton plants in Pakistan, China, and Egypt - Muhammad Z. Ahmed; Shun-Xiang Ren; Nasser S. Mandour; M. N. Maruthi; Muhammad Naveed; Bao-Li Qiu (Journal of Pest Science, 2010)

Comparative effectiveness of Pseudomonas and Serratia sp. containing ACC-deaminase for improving growth and yield of wheat (Triticum aestivum L.) under salt-stressed conditions - Zahir Ahmad Zahir; Usman Ghani; Muhammad Naveed; Sajid Mahmood Nadeem; Hafiz Naeem Asghar (Archives of Microbiology, 2009)

Estimation of Toxic Metals in Scalp Hair Samples of Chronic Kidney Patients - Tasneem Gul Kazi; Nusrat Jalbani; Naveed Kazi; Muhammad Balal Arain; Muhammad Khan Jamali; Hassan Imran Afridi; Ghulam Abbas Kandhro; Raja Adil Sarfraz; Abdul Qadir Shah; Rehana Ansari (Biological Trace Element Research, 2009)

Novel mutations in G protein-coupled receptor gene (P2RY5) in families with autosomal recessive hypotrichosis (LAH3) - Zahid Azeem; Musharraf Jelani; Gul Naz; Muhammad Tariq; Naveed Wasif; Syed Kamran-ul-Hassan Naqvi; Muhammad Ayub; Masoom Yasinzai; Muhammad Amin-ud-din; Abdul Wali; Ghazanfar Ali; Muhammad Salman Chishti; et al. (Human Genetics, 2008)

Contribution of cultivated crops, vegetables, weeds and ornamental plants in harboring of Bemisia tabaci (Homoptera: Aleyrodidae) and associated parasitoids (Hymenoptera: Aphelinidae) in cotton agroecosystem in Pakistan - Muhammad Naveed; Abdus Salam; Mushtaq Ahmad Saleem (Journal of Pest Science, 2007)

Effect of seedling age and water depth on morphological and physiological aspects of transplanted rice under high temperature - Abdul Aziz Khakwani; Masaaki Shiraishi; Muhammad Zubair; Mohammad Safdar Baloch; Khalid Naveed; Inayatullah Awan (Journal of Zhejiang University-SCIENCE B, 2005)